139La NMR kinetic study of lanthanum(III) complexation with acetohydroxamic acid - van Eldik, Rudi; Zahl, Achim; et al. (European Journal of Inorganic Chemistry, 2002)

[3.2.1] and [4.1.1] isomers of Lehn's [2.2.2] Cryptand: Prediction of ion selectivity by quantum chemical calculations XV** - Ćoćić, Dušan; Manaa, Aliya; Siegl, Selina; Puchta, Ralph; van Eldik, Rudi (Zeitschrift für Anorganische und Allgemeine Chemie, 2021)
Selective alkaline and earth alkaline metal ion encapsulation by two different Lehn-type cryptands, noted as [3.2.1] and [4.1.1], was predicted and between them compared on the DFT (B3LYP/LANL2DZp) basis set. Since these cryptands are isomers to the well-known [2.2.2] cryptand, the cation encapsulation selectivity of all three cages were compared. The ion selectivity and ability of the host to adjust their structure to successfully accommodate the metal ions, were based on energy and geometric criteria. Different lengths of O-Et-O-bridging arms provide an unsymmetrical cryptand host with great flexibility to accommodate large alkali and alkaline earth metal cations.
CRIS-Team Scopus Importer:2021-04-02
Keywords: cryptand; DFT-study; selective ion complexation

7Li-NMR determination of stability constants as a function of temperature for lithium-crown ether complexes in a molten salt mixtures - Zahl, Achim; van Eldik, Rudi; et al. (Journal of Physical Chemistry, 1994)
The stability constants of several crown ethers with lithium ion were determined by Li-NMR measurements. A room temperature, basic molten salt of the compostion of 55/45 mol % 1-methyl-3-ethyl-imidazolium chloride to aluminum (III) chloride was used as solvent. On the basis of a 1:1 complex formation the following order was found for the stability constants of the investigated crown ethers: 18-crown-6 < 12-crown-4 < benzo-15-crown-5 < 15-crown-5. A temperature dependence study for 12-crown-4, benzo-15-crown-5, and 15-crown-5 was undertaken for the range 5-84°C. Values of ΔH and ΔS were calculated. At 5.5°C the splitting of the single, fast exchange peak into two separate signals was observed for benzo-15-crown-5, providing further evidence for the formation of the 1:1 complex.

A compact high pressure unit for UV-VIS-NIR spectroscopic measurements at pressures up to 400 MPa - van Eldik, Rudi; Khoshtariya, Dimitri E.; Igel, Peter; Weller, Manfred; Zahl, Achim; et al. (Review of Scientific Instruments, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.laoc1.acompa

A comparative mechanistic study of the reversible binding of NO to a water-soluble octa-cationic FeIII porphyrin complex - Jee, Joo-Eun; Wolak, Maria; Balbinot, Domenico; Jux, Norbert; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2006)
The water-soluble, non-μ-oxo dimer-forming porphyrin, [5,10,15,20-tetrakis-4′-t-butylphenyl-2′,6′-bis-(N-methylene- (4″-t-butylpyridinium))porphyrinato]iron(III) octabromide, (P )Fe, with eight positively charged substituents in the ortho positions of the phenyl rings, was characterized by UV-vis and H NMR spectroscopy and O NMR water-exchange studies in aqueous solution. Spectrophotometric titrations of (P)Fe indicated a pK value of 5.0 for coordinated water in (P)Fe(HO). The monohydroxo-ligated (P)Fe(OH)(HO) formed at 5 < pH < 12 has a weakly bound water molecule that undergoes an exchange reaction, k = 2.4 × 10 s, significantly faster than water exchange on (P)Fe (HO), viz. k = 5.5 × 10 s at 25°C. The porphyrin complex reacts with nitric oxide to yield the nitrosyl adduct, (P)Fe (NO)(L) (L = HO or OH). The diaqua-ligated (P)Fe(HO) binds and releases NO according to a dissociatively activated mechanism, analogous to that reported earlier for other (P)Fe(H O) complexes. Coordination of NO to (P )Fe(OH)(HO) at high pH follows an associative mode, as evidenced by negative ΔS and ΔV values measured for this reaction. The observed ca. 10-fold decrease in the NO binding rate on going from six-coordinate (P)Fe(HO) (k = 15.1 × 10 M s) to (P)Fe(OH)(HO) (k = 1.56 × 10 M s at 25°C) is ascribed to the different nature of the rate-limiting step for NO binding at low and high pH, respectively. The results are compared with data reported for other water-soluble iron(III) porphyrins with positively and negatively charged meso substituents. Influence of the porphyrin periphery on the dynamics of reversible NO binding to these (P)Fe complexes as a function of pH is discussed on the basis of available experimental data. © 2006 American Chemical Society.

Activation volume measurement for C-H activation. Evidence for associative benzene substitution at a platinum(II) center - Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 2002)

A detailed mechanistic study of the substitution behavior of an unusual seven-coordinate iron(III) complex in aqueous solution - Ivanovic-Burmazovic, Ivana; Hamza, Mohamed; van Eldik, Rudi (Inorganic Chemistry, 2002)
A detailed mechanistic study of the substitution behavior of a 3d metal heptacoordinate complex, with a rare pentagonal-bipyramidal structure, was undertaken to resolve the solution chemistry of this system. The kinetics of the complex-formation reaction of [Fe(dapsox)(HO)]ClO (Hdapsox = 2,6-diacetylpyridine-bis(semioxamazide)) with thiocyanate was studied as a function of thiocyanate concentration, pH, temperature, and pressure. The reaction proceeds in two steps, which are both base-catalyzed due to the formation of an aqua-hydroxo complex (pK = 5.78 ± 0.04 and pK = 9.45 ± 0.06 at 25 °C). Thiocyanate ions displace the first coordinated water molecule in a fast step, followed by a slower reaction in which the second thiocyanate ion coordinates trans to the N-bonded thiocyanate. At 25 °C and pH <4.5, only the first reaction step can be observed, and the kinetic parameters (pH 2.5: k = 2.6 ± 0.1 M s, ΔH = 62 ± 3 kJ mol, ΔS = -30 ± 10 J K mol, and ΔV = -2.5 ± 0.2 cm mol) suggest the operation of an I mechanism. In the pH range 2.5 to 5.2 this reaction step involves the participation of both the diaqua and aqua-hydroxo complexes, for which the complex-formation rate constants were found to be 2.19 ± 0.06 and 1172 ± 22 M s at 25 °C, respectively. The more labile aqua-hydroxo complex is suggested to follow an I or D substitution mechanism on the basis of the reported kinetic data. At pH ≥4.5, the second substitution step also can be monitored (pH 5.5 and 25 °C: k = 21.1 ± 0.5 M s, ΔH = 60 ± 2 kJ mol, ΔS = -19 ± 6 J K mol, and ΔV = +8.8 ± 0.3 cm mol, for which an I or D mechanism is suggested. The results are discussed in terms of known structural parameters and in comparison to relevant structural and kinetic data from the literature.

ADVANCES IN INORGANIC CHEMISTRY Medicinal Chemistry Preface - Sadler, Peter J.; van Eldik, Rudi (Advances in Inorganic Chemistry, 2020)
CRIS-Team WoS Importer:2020-06-05

A high-pressure NMR probehead for measurements at 400 MHz - Zahl, Achim; Neubrand, Anton; Aygen, Sitke; van Eldik, Rudi (Review of Scientific Instruments, 1994)

A new enantiomerization mechanism for tripodal penta-coordinate Zn-II(nta) complexes. Theoretical clarification of the observed H-1 NMR spectrum - Puchta, Ralph; van Eikema Hommes, Nico; Meier, Roland; van Eldik, Rudi (Dalton Transactions, 2006)
Based on DFT calculations (RB3LYP/LANL2DZp), the unexpected single-line H-1 NMR spectrum of Zn-II (nta), nta = 2,2',2"-nitrilotriacetate, can be ascribed to a non-dissociative enantiornerization process (delta delta delta reversible arrow lambda lambda lambda) from C, via C-3v to C-3' symmetry. The energy barrier is rather low and depends to a lesser extent on the nature of the co-ligand in [Zn(nta)X](2-) (X: H-, CH3- NH2-, OCH3-, F-, Cl-, Br-, I-) and [Zn(nta)Y](-) (Y:NCH, CO, N-2, O(CH3)(2)), but more so on the overall charge of the complex. The energy barrier for enantiornerization of [Zn(nta)X](2-) is between 5.7 and 6.7 kcal mol(-1), and for [Zn(nta)Y](-) between 2.2 and 3.1 kcal mol(-1).

A new high-pressure NMR probe designed for a narrow bore magnet system - van Eldik, Rudi; Weller, Manfred; Zahl, Achim; Igel, Peter (Review of Scientific Instruments, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.laoc1.anewhi

A New Trigonal-Bipyramidal [Cu-II(pytBuN(3))Cl-2] Complex: Synthesis, Structure and Ligand Substitution Behaviour - Shaban, Shaban Abd El Fattah Youssef; Heinemann, Frank Wilhelm; van Eldik, Rudi (European Journal of Inorganic Chemistry, 2009)
The synthesis, structure and ligand substitution mechanism of a new five-coordinate copper(II) complex with a sterically constrained pytBuN(3) chelate ligand [pytBuN(3) = 2,6-bis(3,5di-tert-butylphenyhminomethyl)pyridine] are reported. In the crystal structure of the complex the [Cu(pytBuN(3))Cl-2] chromophore possesses a distorted trigonal-bipyramidal coordination geometry. The kinetics and mechanism of chloride substitution by thiourea (TU) and N,N,N',N'-tetramethylthiourea (TMTU) were studied in detail as a function of nucleophile concentration, temperature and pressure in methanol as solvent. The kinetics showed that the substitution reaction of [Cu(pytBuN(3))Cl-2] is a biphasic process that involves the subsequent displacement of both chloride ligands. The substitution of the first chloride by TU, k(1)(296) = 918 +/- 30 M-1 s(-1), is 570 times faster than the substitution of the second chloride, k(2)(296) = 1.62 +/- 0.06 M-1 s(-1). Substitution of chloride by TU is characterized by the activation parameters: Delta H-# = 42 2 and 58 +/- 2 kJmol(-1), Delta S-# = -46 +/- 7 and -47 +/- 6 J K(-1)mol(-1), and Delta V-# = -6.5 +/- 0.2 and -5.3 +/- 0.7 cm(3)mol(-1), for the first and second substitution reactions, respectively. It is concluded from the activation parameters that both reactions follow an associative interchange (I-a) mechanism. When the substitution reaction was carried out with the sterically hindered nucleophile TMTU, the rate constant for the displacement of the first chloride, k(2)(296) = 6.9 +/- 0.5 M-1 s(-1), was more than 133 times slower than for the reaction with TU, which further supports the I-a nature of the substitution mechanism. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)
Keywords: Copper; Chelates; Copper(II) complexes; Kinetics; UV/Vis spectroscopy; Biphasic reaction

A Personal Account on Inorganic Reaction Mechanisms - Polaczek, Justyna; Kieca, Konrad; Oszajca, Maria; Impert, Olga; Katafias, Anna; Chatterjee, Debabrata; Ćoćić, Dušan; Puchta, Ralph; Stochel, Grażyna; Hubbard, Colin D.; van Eldik, Rudi (Chemical Record, 2023)
The presented Review is focused on the latest research in the field of inorganic chemistry performed by the van Eldik group and his collaborators. The first part of the manuscript concentrates on the interaction of nitric oxide and its derivatives with biologically important compounds. We summarized mechanistic information on the interaction between model porphyrin systems (microperoxidase) and NO as well as the recent studies on the formation of nitrosylcobalamin (CblNO). The following sections cover the characterization of the Ru(II)/Ru(III) mixed-valence ion-pair complexes, including Ru(II)/Ru(III)(edta) complexes. The last part concerns the latest mechanistic information on the DFT techniques applications. Each section presents the most important results with the mechanistic interpretations.
CRIS-Team Scopus Importer:2023-10-20

A theoretical mechanistic study of [K ⊂ [2.2.2]]+ enantiomerization - Balovic, Jelena; Cocic, Dusan; Dordevic, Sladana; Radenkovic, Slavko; van Eldik, Rudi; Puchta, Ralph (Journal of Physical Organic Chemistry, 2021)
Density functional calculations at three different levels of theory (B3LYP/LANL2DZp, B3LYP-GD3/LANL2DZp, and ωB97XD/def2tzvp) were applied to different conformers of the Lehn-type macrobicyclic polyether cryptate complex [K ⊂ [2.2.2]]+ to construct the enantiomerization pathway and to compute the energy barrier for the change in symmetry. Changes in the conformation of the investigated complex are discussed in terms of energy and geometric criteria, where changes in the structures follow a trend of activation energies prohibiting the achiral pathways. The investigated D3-symmetric cryptate [K ⊂ [2.2.2]]+ shows enantiomerization through an all chiral five step pathway with two local minima (C2 and C2′) and three C1 transition states ending in the D3′-symmetric cryptate [K ⊂ [2.2.2]]+, the mirror image of the starting structure. The potential achiral transition states are higher order saddle points with a minimum twice as high in energy as an all-chiral path. This study unambiguously accounts for Lehn's NMR data showing fluxionality of the studied complex. The obtained results were further rationalized by means of energy decomposition analysis (EDA) and natural bond orbital (NBO) calculations performed for the metal cation and the host in its different conformations.
CRIS-Team Scopus Importer:2021-10-08
Keywords: cryptand; DFT study; EDA; enantiomerization; NBO

BSA Interaction, Molecular Docking, and Antibacterial Activity of Zinc(II) Complexes Containing the Sterically Demanding Biomimetic N3S2 Ligand: The Effect of Structure Flexibility - Soliman, Eman; Ibrahim, Mohamed M.; El-Khouly, Mohamed E.; El-Mehasseb, Ibrahim; Ramadan, Abd El-Motaleb M.; Mahfouz, Magdy E.; Shaban, Shaban Y.; van Eldik, Rudi (Molecules, 2022)
Two zinc(II) complexes, DBZ and DBZH(4), that have (ZnN3S2) cores and differ in the bridging mode of the ligating backbone, effectively bind to BSA. The binding affinity varies as DBZ > DBZH(4) and depends on the ligand structure. At low concentrations, both complexes exhibit dynamic quenching, whereas at higher concentrations they exhibit mixed (static and dynamic) quenching. The energy transfer mechanism from the BSA singlet excited state to DBZ and DBZH(4), is highly likely according to steady-state fluorescence and time-correlated singlet photon counting. Molecular docking was used to support the mode of interaction of the complexes with BSA and showed that DBZ had more energy for binding. Furthermore, antibacterial testing revealed that both complexes were active but to a lesser extent than chloramphenicol. In comparison to DBZH(4), DBZ has higher antibacterial activity, which is consistent with the binding constants, molecular docking, and particle size of adducts. These findings may have an impact on biomedicine.
CRIS-Team WoS Importer:2022-06-24

Can a Nonorganometallic Ruthenium(II) Polypyridylamine Complex Catalyze Hydride Transfer? Mechanistic Insight from Solution Kinetics on the Reduction of Coenzyme NAD+ by Formate - Chrzanowska, Marta; Katafias, Anna; van Eldik, Rudi (Inorganic Chemistry, 2020)
Application of organometallic ruthenium(II) arene complexes has been successful for the modulation of cellular redox processes via their interaction with species such as formate to control the NAD+/NADH balance in cells. Here we present the first evidence that similar effects can be reached with the application of a nonorganometallic ruthenium(II) polypyridyl complex. Kinetic studies performed demonstrate the ability of [RuII(terpy)(en)(H2O/EtOH)]2+ in water/ethanol (1:9, v/v) solution, where terpy = 2,2':6',2″-terpyridine and en = ethylenediamine, to catalyze the reduction of the NAD+ coenzyme to NADH in the presence of formate as hydride transfer source. In this case, terpy instead of arene is responsible for the labilization of coordinated solvent. The suggested catalytic cycle begins with the fast anation of the [RuII(terpy)(en)(H2O/EtOH)]2+ complex by formate. This is followed by the rate-determining formate-catalyzed decarboxylation of the generated ruthenium(II) formato complex to form [RuII(terpy)(en)H]+. Rapid hydride transfer to NAD+ from [RuII(terpy)(en)H]+ to form NADH and to regenerate the starting ruthenium(II) solvato complex, closes the overall catalytic cycle.
CRIS-Team Scopus Importer:2020-10-30

Can Particulate Matter and Nano Metal Oxide Particles Affect the Redox Cycling of Nitrosylcobalamin in Weakly Acidic Aqueous Solution? - Polaczek, Justyna; Stochel, Grazyna; van Eldik, Rudi (European Journal of Inorganic Chemistry, 2021)
Since air pollution is one of the most serious environmental problems, the study of the effects of particulate matter (PM) on physiological processes remains to be an important challenge for scientific communities. The presented studies form part of the project 'Air Pollution versus Autoimmunity: Role of multiphase aqueous Inorganic Chemistry'. In these studies we examined the effect of Standard Reference Material 1648a, supplied by the US National Institute of Standards and Technology (NIST), and its inorganic constituents on the formation of nitrosylcobalamin (CblNO) in the reaction between nitrocobalamin (CblNO(2)) and ascorbic acid in a weakly acidic medium. We monitored the reaction in the presence of urban NIST PM (SRM 1648a), plasma treated NIST PM (LAP) and a number of metal oxide nanoparticles, including redox active metal oxides. The obtained results clearly demonstrated that the presence of these different nanoparticles affected the rate of formation of CblNO but did not affect the nature of the final product. Special attention was given to systematic studies on the role of inorganic nanoparticles as a part of the selected PM in the reaction between CblNO(2) and ascorbic acid.
CRIS-Team WoS Importer:2021-06-11

Catalysis in Biomass Conversion Preface - Ford, Peter C.; van Eldik, Rudi (Advances in Inorganic Chemistry, 2021)
CRIS-Team WoS Importer:2022-02-25

Cation-independent electron transfer between ferricyanide and ferrocyanide ions in aqueous solution - Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 2002)

Characterization of a Mixed-Valence Ru(II)/Ru(III) Ion-Pair Complex. Unexpected High-Frequency Electron Paramagnetic Resonance Evidence for Ru(III)-Ru(III) Dimer Coupling - Impert, Olga; Kozakiewicz, Anna; Wrzeszcz, Grzegorz; Katafias, Anna; Bieńko, Alina; van Eldik, Rudi; Ozarowski, Andrew (Inorganic Chemistry, 2020)
In this contribution, we report the synthesis and full characterization of the first mixed-valence Ru(II)/Ru(III) ion-pair complex, [RuII(bipy)2(pic)]+[cis-RuIIICl2(pic)2]-, in the solid state and in aqueous solution, where bipy = 2,2′-bipyridine and pic- = picolinate. In addition, unexpected high-frequency electron paramagnetic resonance evidence for interactions between two neighboring Ru(III) ions, resulting in a triplet state, S = 1, was found.
CRIS-Team Scopus Importer:2020-06-09

Chelate electronic properties control the redox behaviour and superoxide reactivity of seven-coordinate manganese(II) complexes - Liu, Gaofeng; Dürr, Katharina L.; Puchta, Ralph; Heinemann, Frank Wilhelm; van Eldik, Rudi; Ivanovic-Burmazovic, Ivana (Dalton Transactions, 2009)
We have synthesized and characterized two Mn(II) seven-coordinate complexes with N5 pentadentate ligands, which contain hydrazone and hydrazide groups respectively. We have shown that insertion of hydrazido (amido) groups into the ligand sphere increases the negative charge of the chelate, without changing a donor atom set and coordination geometry, and radically modulate a redox activity of seven-coordinate manganese complexes, which is important for the function of manganese as a superoxide dismutase catalytic center. © 2009 The Royal Society of Chemistry.

Chlorophyll a pi-Cation Radical as Redox Mediator in Superoxide Dismutase (SOD) Mimetics - Orzel, Lukasz; Rutkowska-Zbik, Dorota; van Eldik, Rudi; Fiedor, Leszek; Stochel, Grazyna (ChemPhysChem, 2021)
The extensive speciation of copper(II) chloride in organic solvents varies with concentration, temperature, pressure and oxygen content, providing the ability to switch between different chlorophyll transmetalation pathways. We found that one of them is exceptionally suitable for the formation and stabilisation of the chlorophyll pi-cation radical. This is due to unique redox cycling, which is coupled to the generation and transformation of various reactive oxygen species. In the presence of a proton donor, our system shows behavior which resembles that of superoxide dismutase (SOD). Regardless of light, chlorophyll acts as an electron transfer mediator.
CRIS-Team WoS Importer:2021-02-05

Combined experimental and theoretical study on the reactivity of Compounds I and II in horseradish peroxidase biomimetics - Ji, Li; Franke, Alicja; Brindell, Małgorzata; Oszajca, Maria; Zahl, Achim; van Eldik, Rudi (Chemistry - A European Journal, 2014)
For the exploration of the intrinsic reactivity of two key active species in the catalytic cycle of horseradish peroxidase (HRP), Compound I (HRP-I) and Compound II (HRP-II), we generated in situ [FeIV=O(TMP+•)(2-MeIm)] + and [FeIV=O(TMP)(2-MeIm)]0 (TMP = 5,10,15,20-tetramesitylporphyrin; 2-MeIm = 2-methylimidazole) as biomimetics for HRP-I and HRP-II, respectively. Their catalytic activities in epoxidation, hydrogen abstraction, and heteroatom oxidation reactions were studied in acetonitrile at -15 °C by utilizing rapid-scan UV/Vis spectroscopy. Comparison of the secondorder rate constants measured for the direct reactions of the HRP-I and HRP-II mimics with the selected substrates clearly confirmed the outstanding oxidizing capability of the HRP-I mimic, which is significantly higher than that of HRP-II. The experimental study was supported by computational modeling (DFT calculations) of the oxidation mechanism of the selected substrates with the involvement of quartet and doublet HRP-I mimics (2,4Cpd I) and the closed-shell triplet spin HRP-II model (3Cpd II) as oxidizing species. The significantly lower activation barriers calculated for the oxidation systems involving 2,4Cpd I than those found for 3Cpd II are in line with the much higher oxidizing efficiency of the HRP-I mimic proven in the experimental part of the study. In addition, the DFT calculations show that all three reaction types catalyzed by HRP-I occur on the doublet spin surface in an effectively concerted manner, whereas these reactions may proceed in a stepwise mechanism with the HRP-II mimic as oxidant. However, the high desaturation or oxygen rebound barriers during C-H bond activation processes by the HRP-II mimic predict a sufficient lifetime for the substrate radical formed through hydrogen abstraction. Thus, the theoretical calculations suggest that the dissociation of the substrate radical may be a more favorable pathway than desaturation or oxygen rebound processes. Importantly, depending on the electronic nature of the oxidizing species, that is, 2,4Cpd I or 3Cpd II, an interesting region-selective conversion phenomenon between sulfoxidation and H-atom abstraction was revealed in the course of the oxidation reaction of dimethylsulfide. The combined experimental and theoretical study on the elucidation of the intrinsic reactivity patterns of the HRP-I and HRP-II mimics provides a valuable tool for evaluating the particular role of the HRP active species in biological systems.
Created from Fastlane, Scopus look-up
Keywords: Compound I; Compound II; Horseradish peroxidase; Kinetics; UV/Vis spectroscopy

Combined Low Temperature Rapid Scan and 1H NMR Mechanistic Study of the Protonation and Subsequent Benzene Elimination from a (Diimine)platinum(II) Diphenyl Complex Relevant to Arene C-H Activation Parmene, J.; Ivanovic-Burmazovic, I.; Tilset, M.; van Eldik, R. Inorg. Chem., 2009, 48 (19), 9092-9103 - Parmene, J.; Ivanovic-Burmazovic, Ivana; Tilset, M.; van Eldik, Rudi (Inorganic Chemistry, 2009)
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.lbioch.combin

Compact high pressure unit for ultraviolet-visible-near-infrared spectroscopic measurements at pressures up to 400 MPa - Zahl, Achim; Igel, Peter; Weller, Manfred; Khoshtariya, Dimitri E.; Hamza, Mohamed; van Eldik, Rudi (Review of Scientific Instruments, 2003)

Computational Chemistry Preface - van Eldik, Rudi; Puchta, Ralph (Advances in Inorganic Chemistry, 2019)
CRIS-Team WoS Importer:2019-12-27

Coordination of 1,10-phenanthroline and 2,2′-bipyridine to Li + in different ionic liquids. how innocent are ionic liquids? - Schmeißer, Matthias; Heinemann, Frank Wilhelm; Illner, Peter; Puchta, Ralph; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2011)

Coordination of 1,10-phenanthroline and 2,2'-bipyridine to Li+ in different ionic liquids. How innocent are ionic liquids? - Schmeißer, Matthias; Heinemann, Frank Wilhelm; Illner, Peter; Puchta, Ralph; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2011)
On the basis of (7)Li NMR measurements, we have made detailed studies on the influence of the ionic liquids [emim][NTf(2)], [emim][ClO(4)], and [emim][EtSO(4)] on the complexation of Li(+) by the bidentate N-donor ligands 2,2'-bipyridine (bipy) and 1,10-phenanthroline (phen). For each of the employed ionic liquids the NMR data implicate the formation of [Li(bipy)(2)](+) and [Li(phen)(2)](+), respectively. X-ray diffraction studies were performed to determine the coordination pattern in the solid state. In the case of [emim][ClO(4)] and [emim][EtSO(4)], crystal structures confirmed the NMR data, resulting in the complexes [Li(bipy)(2)ClO(4)] and [Li(phen)(2)EtSO(4)], respectively. On the contrary, the ionic liquid [emim][NTf(2)] generated the C(i) symmetric, dinuclear, supramolecular cluster [Li(bipy)(NTf(2))](2), where the individual Li(+) centers were found to be bridged by two [NTf(2)] anions. Density functional theory (DFT)-calculations lead to further information on the effect of stacking on the coordination geometry of the Li(+) centers.

Coordination of terpyridine to Li+ in two different ionic liquids - Pokorny, Klaus; Schmeißer, Matthias; Hampel, Frank; Zahl, Achim; Puchta, Ralph; van Eldik, Rudi (Inorganic Chemistry, 2013)

Detailed mechanistic information on methane elimination from a methyl(hydrido)platinum(IV) complex. Relevance for the mechanism of methane activation - Fekl, Ulrich; Zahl, Achim; van Eldik, Rudi (Organometallics, 1999)

Discrimination of diverse (pressure/temperature-dependent/independent) inherent sub-structures in liquid water (D2O) from difference vibrational spectroscopy - Zahl, Achim; Neubrand, Anton; van Eldik, Rudi; et al. (Journal of Physical Chemistry B, 2004)

DNA Binding and Cleavage, Stopped-Flow Kinetic, Mechanistic, and Molecular Docking Studies of Cationic Ruthenium(II) Nitrosyl Complexes Containing "NS4" Core - Shereef, Hadeer A.; Moemen, Yasmine S.; Elshami, Fawzia I.; El-Nahas, Ahmed M.; Shaban, Shaban Y.; van Eldik, Rudi (Molecules, 2023)
This work aimed to evaluate in vitro DNA binding mechanistically of cationic nitrosyl ruthenium complex [RuNOTSP]+ and its ligand (TSPH2) in detail, correlate the findings with cleavage activity, and draw conclusions about the impact of the metal center. Theoretical studies were performed for [RuNOTSP]+, TSPH2, and its anion TSP-2 using DFT/B3LYP theory to calculate optimized energy, binding energy, and chemical reactivity. Since nearly all medications function by attaching to a particular protein or DNA, the in vitro calf thymus DNA (ctDNA) binding studies of [RuNOTSP]+ and TSPH2 with ctDNA were examined mechanistically using a variety of biophysical techniques. Fluorescence experiments showed that both compounds effectively bind to ctDNA through intercalative/electrostatic interactions via the DNA helix's phosphate backbone. The intrinsic binding constants (Kb), (2.4 ± 0.2) × 105 M-1 ([RuNOTSP]+) and (1.9 ± 0.3) × 105 M-1 (TSPH2), as well as the enhancement dynamic constants (KD), (3.3 ± 0.3) × 104 M-1 ([RuNOTSP]+) and (2.6 ± 0.2) × 104 M-1 (TSPH2), reveal that [RuNOTSP]+ has a greater binding propensity for DNA compared to TSPH2. Stopped-flow investigations showed that both [RuNOTSP]+ and TSPH2 bind through two reversible steps: a fast second-order binding, followed by a slow first-order isomerization reaction via a static quenching mechanism. For the first and second steps of [RuNOTSP]+ and TSPH2, the detailed binding parameters were established. The total binding constants for [RuNOTSP]+ (Ka = 43.7 M-1, Kd = 2.3 × 10-2 M-1, ΔG0 = -36.6 kJ mol-1) and TSPH2 (Ka = 15.1 M-1, Kd = 66 × 10-2 M, ΔG0 = -19 kJ mol-1) revealed that the relative reactivity is approximately ([RuNOTSP]+)/(TSPH2) = 3/1. The significantly negative ΔG0 values are consistent with a spontaneous binding reaction to both [RuNOTSP]+ and TSPH2, with the former being very favorable. The findings showed that the Ru(II) center had an effect on the reaction rate but not on the mechanism and that the cationic [RuNOTSP]+ was a more highly effective DNA binder than the ligand TSPH2 via strong electrostatic interaction with the phosphate end of DNA. Because of its higher DNA binding affinity, cationic [RuNOTSP]+ demonstrated higher cleavage efficiency towards the minor groove of pBR322 DNA via the hydrolytic pathway than TSPH2, revealing the synergy effect of TSPH2 in the form of the complex. Furthermore, the mode of interaction of both compounds with ctDNA has also been supported by molecular docking.
CRIS-Team Scopus Importer:2023-04-21
Keywords: binding interaction; DNA; kinetic investigation; molecular docking; reaction mechanism; ruthenium nitrosyl complexes

Effective encapsulation of noble and small gases and molecules by tubularene molecule - Weinert, Christopher; Ćoćić, Dušan; Puchta, Ralph; van Eldik, Rudi (Zeitschrift für Anorganische und Allgemeine Chemie, 2023)
Based on computational chemistry calculations (ωB97XD/def2-tzvp//ωB97XD/def2-svp/svpfit+ZPE(ωB97XD/def2-svp/svpfit)), binding energy of tubular[3,6,6,6]arene to accommodate noble gases and a series of 29 small gases were calculated. Based on the gained results, Rn (−17.52 kcal/mol) from the series of noble gases is best suited to be accommodated. In the series of noble gases, the binding energy increases linearly with increasing gas radii. From the series of 29 small guests, IF3 and C2I2 ( −23 kcal/mol) have the best proclivity to be most effectively accommodated in the tubularene, with other 26 exhibiting favorable encapsulation energies on various scales depending on their voluminosity and structure, and only NI3 with the unfavorable complexation energy of 13.87 kcal/mol. Investigated gases, depending on the size, are placed at the different position inside the tube-like cavity of the tubularene. The structure of the tubularene, independent of the hosted guest species, has remained very rigid, with its atom's rearrangements withing an error margin.
CRIS-Team Scopus Importer:2023-12-22
Keywords: DFT; host-guest chemistry; Noble gases; tubularene

Effect of chelate dynamics on water exchange reactions of paramagnetic aminopolycarboxylate complexes - Maigut, Joachim; Meier, Roland; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2008)
Because of our interest in evaluating a possible relationship between complex dynamics and water exchange reactivity, we performed H NMR studies on the paramagnetic aminopolycarboxylate complexes Fe-TMDTA and Fe-CyDTA and their diamagnetic analogues Zn-TMDTA and Zn-CyDTA. Whereas a fast Δ-Δ isomerization was observed for the TMDTA species, no acetate scrambling between in-plane and out-of-plane positions is accessible for any of the CyDTA complexes because the rigid ligand backbone prevents any configurational changes in the chelate system. In variable-temperature H NMR studies, no evidence of spectral coalescence due to nitrogen inversion was found for any of the complexes in the available temperature range. The TMDTA complexes exhibit the known solution behavior of EDTA, whereas the CyDTA complexes adopt static solution structures. Comparing the exchange kinetics of flexible EDTA-type complexes and static CyDTA complexes appears to be a suitable method for evaluating the effect of ligand dynamics on the overall reactivity. In order to assess information concerning the rates and mechanism of water exchange, we performed variable-temperature and -pressure O NMR studies of Ni-CyDTA, Fe-CyDTA, and Mn-CyDTA. For Ni-CyDTA, no significant effects on line widths or chemical shifts were apparent, indicating either the absence of any chemical exchange or the existence of a very small amount of the water-coordinated complex in solution. For [Fe(CyDTA)(HO)] and [Mn (CyDTA)(HO)], exchange rate constant values of (1.1 ± 0.3) × 10 and (1.4 ± 0.2) × 10 s, respectively, at 298 K were determined from fits to resonance-shift and line-broadening data. A relationship between chelate dynamics and reactivity seems to be operative, since the CyDTA complexes exhibited significantly slower reactions than their EDTA counterparts. The variable-pressure O NMR measurements for [Mn(CyDTA) (HO)] yielded an activation volume of +9.4 ± 0.9 cm mol. The mechanism is reliably assigned as a dissociative interchange (I) mechanism with a pronounced dissociation of the leaving water molecule in the transition state. In the case of [Fe(CyDTA)(HO)], no suitable experimental conditions for variable-pressure measurements were accessible. © 2008 American Chemical Society.

Effect of pressure on proton-coupled electron transfer reactions of seven-coordinate iron complexes in aqueous solutions - Sarauli, David; Meier, Roland; Liu, Gaofeng; Ivanovic-Burmazovic, Ivana; van Eldik, Rudi (Inorganic Chemistry, 2005)
For the first time, the effect of pressure on proton-coupled electron-transfer reactions of two selected seven-coordinate Fe (HL)(HO) systems [where HL = 2,6-diacetylpyridine-bis(semicarbazone) and 2,6-diacetylpyridine-bis(semioxamazide), respectively] was examined. The acid-base equilibria of the different Fe systems were investigated by spectrophotometric, potentiometric, and electrochemical titrations. On the basis of the obtained species distributions, the pH intervals in which the different protonated forms of the two studied systems exist were defined. In different pH ranges, a different number of protons (from 0 to 3 protons per electron) can be transferred during the redox process, which affects the change in the overall charge on the complexes. For all the different protonation forms of the studied complexes, the change in the redox potentials with pressure was measured and the redox reaction volume was obtained by high-pressure cyclic voltammetry. The results show that in the case of proton-coupled electron transfer, the reaction volume for the neutralization of protons contributes to the overall reaction volume. A linear correlation between Δz (change in the square of the charge) and the overall reaction volume of the complexes upon reduction, ΔV, was found. The average value of the intrinsic volume change for the selected seven-coordinate iron complexes was estimated from the intercept of the plot of ΔV versus Δz to be 9.2 ± 0.7 cm mol. For the combined redox and protonation processes, the data are discussed in terms of linear correlations between Δz and the redox and neutralization reaction volumes reported in the literature. © 2005 American Chemical Society.

Electrochemistry of Ru(edta) complexes relevant to small molecule transformations: Catalytic implications and challenges - Chatterjee, Debabrata; Oszajca, Maria; Katafias, Anna; van Eldik, Rudi (Coordination Chemistry Reviews, 2021)
Electrochemistry of Ru(edta) complexes (edta4− = ethylenediaminetetraacetate) progressed over a period of several decades, with significant increase in understanding of the electro-catalytic processes involving the substrate coordinated to the metal center. While electrochemistry studies of many Ru(edta) complexes were published in several papers, no attempt has been made to provide a comprehensive and systematic overview of its electrochemical properties, evaluating its application to catalytic electrochemical transformation of small molecules. In this article, results of the electrochemical studies of both mononuclear and binuclear complexes of Ru(edta) are reviewed with regard to electron-transfer reaction mechanism and activity. Their potential to act as redox mediators or catalysts in electrochemical transformations of small molecules and enzymatic reactions, are highlighted. This review aims to contribute to the mechanistic understanding of Ru(edta) complexes in catalysis of such electrochemical transformations.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Binuclear complexes; Electrochemistry; Mononuclear complexes; Ru(edta); Small molecule activation

Electron transfer reactions of RuIII(edta) containing the n-heterocyclic ligand pyrazine: Kinetic and mechanistic studies - Chatterjee, Debabrata; van Eldik, Rudi (Journal Macroheterocycles, 2020)
Electron transfer reactions involving Ru(III) complexes pioneered by Nobel Laureate Henry Taube in the ‘late sixties’, has been an area of continued research for more than the past five decades. This review focuses on the research progress in the use of a Ru(III) complex containing the ‘edta’ ligand (edta4– = ethylenediaminetetraacetate) in electron transfer processes, and mainly covers the electron transfer reaction of [RuIII(edta)(pz)]– (pz = pyrazine) with biologically important reductants, viz. L-ascorbic acid, catechol, sulfite, sulfide and thiols, highlighting the authors’ own research work. The scope of this review is to contribute to the mechanistic understanding of electron transfer reactions of [RuIII(edta)(pz)]– with aforementioned biologically important electron donors, and to illustrate the preferential reaction pathway(s).
CRIS-Team Scopus Importer:2020-12-18
Keywords: Biologically important reductants; Electron-transfer; Pyrazine; Reaction mechanism; Redox reaction; Ru(edta)

Electrostatic complexation and photoinduced electron transfer between Zn-Cytochrome c and polyanionic fullerene dendrimers - Braun, Martin; Atalick, Stefan; Guldi, Dirk Michael; Lanig, Harald; Brettreich, Michael; Burghardt, Stephan; Hatzimarinaki, Maria; Ravanelli, Elena; Prato, Maurizio; van Eldik, Rudi; Hirsch, Andreas (Chemistry - A European Journal, 2003)
Two dendritic fullerene (DF) monoadducts, 2 and 3, which can carry up to 9 and 18 negative charges, respectively, were examined with respect to electrostatic complexation with Cytochrome c (Cytc). To facilitate comprehensive photophysical investigations, the zinc analogue of Cytc (ZnCytc) was prepared according to a novel, modified procedure. The association of ZnCytc and DF, and consequential photo-induced electron transfer within ZnCytc-DF from the photoexcited protein to the fullerene, was proven by fluorescence spectroscopy and transient absorption spectroscopy. These findings were also supported by circular dichroism as well as by extensive molecular dynamics (MD) simulations.

Elucidation of the solution structure and water-exchange mechanism of paramagnetic [FeII(edta)(H2O)]2- - Maigut, Joachim; Meier, Roland; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2007)

Encapsulated host-guest dynamics: Bond rotational barriers as a probe of host interior cavity space - Mugridge, J.S.; Raymond, Kenneth; Zahl, Achim; van Eldik, Rudi; Geza, Szigethy; et al. (2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dchph.laoc1.encaps

Equilibrium Studies on Pd(II)–Amine Complexes with Bio-Relevant Ligands in Reference to Their Antitumor Activity - Shoukry, Mohamed M.; van Eldik, Rudi (International Journal of Molecular Sciences, 2023)
This review article presents an overview of the equilibrium studies on Pd-amine complexes with bio-relevant ligands in reference to their antitumor activity. Pd(II) complexes with amines of different functional groups, were synthesized and characterized in many studies. The complex formation equilibria of Pd(amine)2+ complexes with amino acids, peptides, dicarboxylic acids and DNA constituents, were extensively investigated. Such systems may be considered as one of the models for the possible reactions occurring with antitumor drugs in biological systems. The stability of the formed complexes depends on the structural parameters of the amines and the bio-relevant ligands. The evaluated speciation curves can help to provide a pictorial presentation of the reactions in solutions of different pH values. The stability data of complexes with sulfur donor ligands compared with those of DNA constituents, can reveal information regarding the deactivation caused by sulfur donors. The formation equilibria of binuclear complexes of Pd(II) with DNA constituents was investigated to support the biological significance of this class of complexes. Most of the Pd(amine)2+ complexes investigated were studied in a low dielectric constant medium, resembling that of a biological medium. Investigations of the thermodynamic parameters reveal that the formation of the Pd(amine)2+ complex species is exothermic.
CRIS-Team Scopus Importer:2023-03-24
Keywords: bio-relevant ligands; Pd-amine complexes; speciation studies; stability constants; thermodynamic parameters

Evidence for associative ligand exchange processes on solvated lithium cations - Puchta, Ralph; Galle, Michael; van Eikema Hommes, Nico; Pasgreta, Ewa; van Eldik, Rudi (Inorganic Chemistry, 2004)
The ligand exchange mechanism of solvated lithium cations has been studied using DFT calculations (RB3LYP/6-311+G**). The water exchange mechanism on [Li(H2O)(4)](+) was found to be limiting associative (A) involving a five-coordinate intermediate, whereas ammonia exchange on [Li(NH3)(4)](+) was found to follow an associative interchange (I-a) mechanism. The suggested mechanisms are discussed in reference to available experimental and theoretical data.

Evidence for interchange ligand-exchange processes on solvated beryllium cations - Puchta, Ralph; van Eikema Hommes, Nico; van Eldik, Rudi (Helvetica Chimica Acta, 2005)
The ligand-exchange mechanism of solvated Be2+ cations has been studied by means of DFT calculations (RB3LYP/6-311 + G**). Ligand exchange around [BeL4](2+), where L = H2O, NH3, CO2, formaldehyde (H2CO), HCN, N-2, and CO, was found to follow an associative interchange (I.) process in all cases. The size of the activation barrier is almost independent of the type of donor atom, and depends mainly on the hybridization undergone by the donor atom. This, in turn, suggests that steric effects play a major role in solvent- and ligand-exchange reactions in Be2+ systems.

Experimental and Computational Insight into the Mechanism of NO Binding to Ferric Microperoxidase. The Likely Role of Tautomerization to Account for the pH Dependence - Oszajca, Maria; Drabik, Gabriela; Radoń, Mariusz; Franke, Alicja; van Eldik, Rudi; Stochel, Grażyna (Inorganic Chemistry, 2021)
According to the current paradigm, the metal-hydroxo bond in a six-coordinate porphyrin complex is believed to be significantly less reactive in ligand substitution than the analogous metal-aqua bond, due to a much higher strength of the former bond. Here, we report kinetic studies for nitric oxide (NO) binding to a heme-protein model, acetylated microperoxidase-11 (AcMP-11), that challenge this paradigm. In the studied pH range 7.4-12.6, ferric AcMP-11 exists in three acid-base forms, assigned in the literature as [(AcMP-11)FeIII(H2O)(HisH)] (1), [(AcMP-11)FeIII(OH)(HisH)] (2), and [(AcMP-11)FeIII(OH)(His-)] (3). From the pH dependence of the second-order rate constant for NO binding (kon), we determined individual rate constants characterizing forms 1-3, revealing only a ca. 10-fold decrease in the NO binding rate on going from 1 (kon(1) = 3.8 × 106 M-1 s-1) to 2 (kon(2) = 4.0 × 105 M-1 s-1) and the inertness of 3. These findings lead to the abandonment of the dissociatively activated mechanism, in which the reaction rate can be directly correlated with the Fe-OH bond energy, as the mechanistic explanation for the process with regard to 2. The reactivity of 2 is accounted for through the existence of a tautomeric equilibrium between the major [(AcMP-11)FeIII(OH)(HisH)] (2a) and minor [(AcMP-11)FeIII(H2O)(His-)] (2b) species, of which the second one is assigned as the NO binding target due to its labile Fe-OH2 bond. The proposed mechanism is further substantiated by quantum-chemical calculations, which confirmed both the significant labilization of the Fe-OH2 bond in the [(AcMP-11)FeIII(H2O)(His-)] tautomer and the feasibility of the tautomer formation, especially after introducing empirical corrections to the computed relative acidities of the H2O and HisH ligands based on the experimental pKa values. It is shown that the "effective lability"of the axial ligand (OH-/H2O) in 2 may be comparable to the lability of the H2O ligand in 1.
CRIS-Team Scopus Importer:2021-09-24

Experimental and theoretical approaches to the protonation of thiourea: A convenient nucleophile in coordination chemistry revisited - Schiessl, Wolfgang; Summa, Nadine; Weber, Christian; Gubo, Sonja; Dücker-Benfer, Carlos; Puchta, Ralph; van Eikema Hommes, Nico; van Eldik, Rudi (Zeitschrift für Anorganische und Allgemeine Chemie, 2005)
The protonation of thiourea was reinvestigated in aqueous and non-aqueous media using potentiometric, UV-vis, NMR, MS spectroscopy, as well as DFT calculations. In aqueous medium, no evidence for protonation could be found in the pH range 0 to 7, in agreement with typical pK(a) values (acid dissociation constants of protonated thiourea) quoted in the literature of around - 1.2. Most of the protonation constants quoted in the literature are incorrect and apparently refer to pK, values. Protonation of thiourea occurs at a much higher pK, value in methanol and in water-dioxane mixtures, which must be related to the stabilization of the protonated species in such media.
Keywords: protonation; thiourea; NMR studies; DFT calculations; solvent effects

Folate titanium (IV)-chitosan nanocomposites as drug delivery system for active-targeted cancer therapy: Design, HSA/GSH binding, mechanistic, and biological investigations - Alsaed, Amera; Elshami, Fawzya I.; Ibrahim, Mohemed M.; Shereef, Hadeer; Mohany, Hany; van Eldik, Rudi; Shaban, Shaban Y. (Journal of Drug Delivery Science and Technology, 2024)
Folate Ti(IV)-chitosan nanocomposite (TiFA@CS NPs) were prepared from folate Ti(IV)-complex (TiFA) and chitosan (CS) with optimum particle size (175 ± 7 nm), high stability (ζ = −25.1 mV), and minimum hemolytic activity to target cells expressing folate receptors. The interaction with Human Serum Albumin (HSA), a target biomolecule, thought to be the primary pharmacological target of anticancer drugs, and Glutathione (GSH) considering that cisplatin resistance could be due to a reaction between cisplatin and GSH, were evaluated and revealed that, although TiFA@CS NPs show strong binding to HSA, compared to TiFA and FA, the former showed weaker binding to GSH and hence exhibits a lower resistant factor. Kinetic stability, affinity, and association constants of compounds-HSA were examined using a stopped-flow method, and the results show that the formulation of TiFA in TiFA@CS NPs alters the binding mechanism while also enhancing the coordination affinity and kinetic stability. Furthermore, in-vitro cytotoxicity revealed that active-targeting TiFA@CS NPs significantly inhibited FR-positive MCF-7 cells compared to FRs-negative A549 cells which in agreement with the binding constants and resistant factor. Moreover, in-vitro TiFA release assays using TiFA@CS NPs in 10 mM GSH, mimicking the tumor microenvironment, revealed increased TiFA release behavior. Together with its coordination affinity, release evaluations, and cytoxicity, TiFA@CS NPs showed good cell death and rapid tumor uptake, making them an excellent alternative for targeted drug delivery by FR.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Biocompatibility; Folate receptors; Nanomedicine; Targetted drugs; Titanium folate

Formation of an association complex without a substitution reaction occurring between methylcobalamin and cyanide - Brasch, NE; Müller, F.; Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 1997)

Generation and photogeneration of hydroxyl radicals and singlet oxygen by particulate matter and its inorganic components - Mikrut, Magdalena; Mazuryk, Olga; Macyk, Wojciech; van Eldik, Rudi; Stochel, Grażyna (Journal of Environmental Chemical Engineering, 2021)
Polluted air containing particulate matter (PM) is a huge environmental problem in the city of Kraków, Poland. PM causes numerous negative health effects including infection of the respiration system and cardiovascular disorders. The development of autoimmune disorders can be facilitated by redox active transition metals due to the generation of reactive oxygen species (ROS) and induction of oxidative stress, which results in lipid peroxidation, protein oxidation and severe oxidative modification of DNA. Our goal was to study ROS generation (in particular, HO• and 1O2) in the presence of PM collected via different procedures at different locations in Kraków. Scanning electron microscopy analysis confirmed that in all collected samples, aggregates of small grains could be observed. Cold plasma treatment was used to remove parts of the organic matter and to uncover inorganic compounds which become more relevant following plasma treatment. All samples were photoactive and showed hydroxyl radical generation. Singlet oxygen production studies indicated that during plasma treatment, unsaturated organic species are produced that intensify the generation of 1O2. Generation of hydroxyl radicals and singlet oxygen in vitro was confirmed using human epithelial cell line A549.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Air pollution; Oxidative stress; Particulate matter; Photocatalysis; Reactive oxygen species

Guest exchange dynamics in an M4L6 tetrahedral host - Zahl, Achim; van Eldik, Rudi; et al. (Journal of the American Chemical Society, 2006)
Guest exchange in an ML supramolecular assembly was previously demonstrated to proceed through a nonrupture mechanism in which guests squeeze through apertures in the host structure and not through larger portals created by partial assembly dissociation. Focusing on the [Ga L] assembly L = 1,5-bis(2′, 3′-dihydroxybenzamido)naphthalene, the host-guest kinetic behavior of this supramolecular capsule is defined. Guest self-exchange rates at varied temperatures and pressures were measured to determine activation parameters, revealing negative ΔS‡ and positive ΔV‡ values PEt: ΔH‡ = 74(3) kJ mol, ΔS‡ = -46(6) J mol K, k = 0.003 s; NEt: ΔH‡ = 69(2) kJ mol, ΔS‡ = -52(5) J mol K, k = 0.009 s; NMePr: ΔH‡ = 52(2) kJ mol, ΔS‡ = -56(7) J mol K, ΔV‡ = +13(1) cm mol, k = 4.4 s; NPr : ΔH‡ = 42(1) kJ mol, ΔS‡ = -102(4) J mol K, ΔV‡ = +31(2) cm mol, k = 1.4 s. In PEt for NEt exchange reactions, egress of the initial guest (G1) is found to be rate determining, with increasing G1 and G2 (the displacing guest) concentrations inhibiting guest exchange. This inhibition is explained by the decreased flexibility of the host imparted by exterior, or exohedral, guest interactions by both the G1 and G2 guests. Blocking the exohedral host sites with high concentrations of the smaller NMe cation (a weak endohedral guest) enhances PEt for NEt guest exchange rates. Finally, guest displacement reactions also demonstrate the sensitivity of guest exchange to thermodynamic endohedral guest binding affinities. When the initial guest (G1) has a weaker affinity for the host, G2 concentration dependence is observed in addition to dependence on the G2 binding strength. © 2006 American Chemical Society.

Gutmann donor and acceptor numbers for ionic liquids - Zahl, Achim; van Eldik, Rudi; Puchta, Ralph; Schmeißer, Matthias; Illner, Peter (Chemistry - A European Journal, 2012)

HCN exchange on [Cu(HCN)(4)](+): a quantum chemical investigation - Alzoubi, Basam; Weber, Immo; Walther, Markus; van Eikema Hommes, Nico; Puchta, Ralph; van Eldik, Rudi (Journal of Coordination Chemistry, 2014)
Density functional (B3LYP, B3PW91, X3LYP, BP86, PBEPBE, PW91PW91, and M06) and ab initio (MP2, MP4sdq, CCSD, and CCSD(T)) calculations with extended basis sets (6-311+G**, TZVP, LANL2DZ+p, and SDD+p, the latter including extra polarization and diffuse functions) indicate that HCN exchange on [Cu(HCN)(4)](+) proceeds via an associative interchange (I-a) mechanism and a D-3h transition structure [Cu(HCN)(5)](+)double dagger. The activation barrier, relative to the model complex [Cu(HCN)(4)](+)center dot HCN, varies modestly, depending on the computational level. Typical values are 8.0 kcalM(-1) (B3LYP/6-311+G**), 6.0 kcalM(-1) (M06/6-311+G**), and 4.8 kcalM(-1) (CCSD(T)/6-311+G**//MP2(full)/6-311+G**). Inclusion of an implicit solvent model (B3LYP(CPCM)/6-311+G**) leads to an activation barrier of 5.8 kcal mol(-1). Comparison of the HCN exchange mechanisms on [Li(HCN)(4)](+)(limiting associative, A) and [Cu(HCN) (4)](+)(associative interchange, I-a) reveals that pi back donation in the equatorial Cu-N bonds in the transition state determines the mechanism.
Keywords: Copper(I); Hydrogen cyanide; Solvent exchange; Mechanism; DFT

Heterogeneous proton-coupled electron transfer in seven-coordinate iron superoxide dismutase mimetics: Concerted mechanism for two-proton one-electron transfer - Sarauli, David; van Eldik, Rudi; Ivanovic-Burmazovic, Ivana (Inorganic Reaction Mechanisms, 2012)
In this work, electrochemical studies on the seven-coordinate iron complex (Fe III/II dapsox), a functional model for the superoxide dismutase enzyme (SOD mimetic), were performed in an aqueous solution over the pH range 1 - 12 (with and without buffers) to conceive the underlying heterogeneous proton-coupled electron transfer (PCET) processes of various complex species. The thermodynamics of the corresponding proton transfer, electron transfer, and PCET processes have been evaluated as well as the kinetics of related heterogeneous electrode reactions of all complex species in solution. Measurements in D 2 O have also been carried out for selected redox couples to assess a possible kinetic isotope effect (KIE). In the case of a two-proton one-electron transfer process in the absence of a buffer, the KIE was found to be 4.8, whereas in the case of a one-proton one-electron transfer process in buffered solutions, an inverse KIE was observed. The overall data suggest the operation of a concerted PCET mechanism for the two-proton one-electron transfer process, whereas involvement of an H-bonded precursor adduct formed between the buffer components, and the complex species within a one-proton one-electron transfer mechanism is feasible. These results shed light on both the enzymatic and the mimetic SOD mechanisms, speaking in favor of the two-proton one-electron transfer process as a desirable mechanism for efficient catalytic superoxide dismutation. © 2012 Walter de Gruyter GmbH, Berlin/Boston.

High-nuclearity ruthenium carbonyl cluster chemistry. 9. Ligand substitution at decaruthenium carbonyl clusters - Randles, Michael D.; Cifuentes, Marie P.; Moxey, Graeme J.; Zahl, Achim; van Eldik, Rudi; Humphrey, Mark G. (Journal of Organometallic Chemistry, 2017)
The mono-to tri-substituted decaruthenium cluster anions [Ru-10(mu-H)(mu(6)-C)(CO)(24-x)(L)(x)](-) [L = P(C6H4Me-4)(3), AsPh3, SbPh3, x = 1-3] were prepared as their [PPh4](+) salts in moderate to good yields from reaction of [PPh4][Ru-10(mu-H)(mu(6)-C)(CO)(24)] with the corresponding group 15 ligands at room temperature in acetone. The tetrakis-substituted cluster Ru-10(mu(6)-C)(mu(3)-CO)(mu-CO)(CO)(19)P(C6H4Me-4)(3)(4) was obtained in high yield from [PPh4](2)[Ru-10(mu(6)-C)(CO)(24)] and an excess of the phosphine under the same conditions; a single-crystal X-ray diffraction study revealed that the phosphines ligate at the vertices of the "giant tetrahedral" core. Kinetics studies of the formation of [PPh4][Ru-10(mu-H)(mu(6)-C)(AsPh3)(2)(CO)(22)] from [PPh4][Ru-10(mu-H)(mu(6)-C)(AsPh3)(CO)(23)] shows that ligand substitution at these giant tetrahedral clusters proceeds via a strongly associative pathway with the likely intermediacy of a Ru-Ru bond-cleaved intermediate. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Ruthenium; High-nuclearity clusters; Kinetics; X-ray structure

High-pressure nuclear magnetic resonance probe designed for a narrow bore magnet system - Zahl, Achim; Igel, Peter; Weller, Manfred; van Eldik, Rudi (Review of Scientific Instruments, 2004)

High-Pressure Oxygen-17 NMR Study of the Dihydroxo-Bridged Rhodium(III) Hydrolytic Dimer. Mechanistic Evidence for Limiting Dissociative Water Exchange Pathways - Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 1998)

High-pressure testing of heterogeneous charge transfer in a room-temperature ionic liquid: Evidence for solvent dynamic control - Dolidze, Tina D.; Khoshtariya, Dimitri E.; Illner, Peter; Kulisiewicz, Leszek; Delgado, Antonio; van Eldik, Rudi (Journal of Physical Chemistry B, 2008)
We report the first application of a high-pressure electrochemical strategy to study heterogeneous charge transfer (CT) in a room-temperature ionic liquid, [BMIM][BTA]. High-pressure kinetic studies on electron exchange for two redox couples of different charge type, viz. [Fe(bipy)3]3+/2+ and [Fe(cp)2]+/0, at bare Au electrodes within the range of 0.1 -150 MPa, revealed large positive volumes of activation that were found to be virtually the same for the two redox couples in terms of the CT rate constants and diffusion coefficients, despite the reactant's charge type. Independent viscosity (fluidity) studies at elevated pressure (up to 175 MPa), were also performed and revealed a pressure coefficient closely resembling the former ones. Complementary temperature-dependent kinetic studies within the range of 298-358 K also revealed the virtual similarity in activation enthalpies for the same kinetic and diffusion processes, as well as the viscosity of [BMIM][BTA]. A rigorous analysis of the complete variety of obtained results strongly indicates that dynamic (frictional) control of CT is operative by way of the full adiabatic mechanism. The contribution of the Franck-Condon term to the activation free energy of the kinetic process seems almost diminished because of the high value of electronic coupling and freezing out of the outer-sphere reorganization energy. Further analyses indicate that frictional control most probably takes place through slow translational modes (implying "minimal volume" cooperative dislocations) of constituent ions. This kind of motion seems further slowed down within the vicinity of the active site presumably located within the diffusive-like zone situated next to the compact (first) part of the metal/ionic liquid junction. © 2008 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2008.tech.ITC.stmmec.highpr

Host-Guest Complexes of Dodeka(ethylene)octamine: Prediction of Ion Selectivity by Quantum Chemical Calculations IX - Puchta, Ralph; Walther, Daniel; März, Matthias; Begel, Svetlana; van Eldik, Rudi (Zeitschrift für Anorganische und Allgemeine Chemie, 2019)
In this contribution we investigated the ion complexation of Bühl's cryptand, dodeka(ethylene)octamine by quantum chemical methods (B3LYP/LANL2DZp). This cryptand is an isomer of a well-known Lehn-type cryptand [TriPip222]. The ion selectivity was determined based on the energetic criteria derived by model reactions starting from solvated metal ions and empty dodeka(ethylene)octamine, and by comparing the M–N bond length in [M ⊂ dodeka(ethylene)octamine]m+ and [M(NH3)6]m+. We calculated that Bühl's cryptand will complex best Na+ followed by Li+ as alkaline cations and Ca2+ followed by Mg2+ as alkaline earth metal ions. Based on this data we conclude that Bühl's cryptand offers a smaller cavity to nest ions than the Lehn-type [TriPip222].
CRIS-Team Scopus Importer:2019-06-18
Keywords: Cryptands; DFT study; Selective ion complexation

Host-guest complexes of the Beer-Can-cryptand: prediction of ion selectivity by quantum chemical calculations XI - Puchta, Ralph; Ćoćić, Dušan; Michel, Martin; van Eldik, Rudi (Journal of Coordination Chemistry, 2019)
Based on DFT calculations (B3LYP/LANL2DZp) and the application of model equations, as well as a comparison of M-N-donor length with an unstrained reference ([M(solvent)6]n+), the selectivity of the alkali and alkaline earth cations (Li+–Cs+ and Be2+–Ba2+) for the recently synthesized cryptand bis-triazacyclononane tris-pyridyl N9-azacryptand (Beer-Can) was investigated. The host can bind the alkali cation K+ best, followed by the alkaline earth cations Ca2+ and Sr2+, and by Na+ and Ba2+. This selectivity pattern is identical to the selectivity of the Lehn-type cryptand [phen.phen.phen], which suggests a similar cavity size. The good flexibility of the Beer-Can is provided by the aza-crown-like top and bottom of the “can,” and the pyridines on the “can-wall.”.
CRIS-Team Scopus Importer:2019-07-23
Keywords: cryptand; DFT study; Selective ion complexation

Host-Guest Complexes of [TriPip222], the Piperazine Analogue of [2.2.2]: Prediction of Ion Selectivity by Quantum Chemical Calculations VIII[#] - Begel, Svetlana; Scheurer, Andreas; Puchta, Ralph; van Eldik, Rudi (Zeitschrift für Anorganische und Allgemeine Chemie, 2016)
Keywords: Cryptand; Complexation; Quantum chemical calculation; Host-guest complex

Host-guest complexes of two imine based isomeric 2-Lehn-type cryptands: prediction of ion selectivity by quantum chemical calculations XIX* - Adel, Alan; Puchta, Ralph; Ćoćić, Dušan; Kolenović Serezlić, Majda; Soldatović, Tanja; van Eldik, Rudi (Journal of Coordination Chemistry, 2025)
In this study the cryptands [2=N.2=N.2=N] and [2N=.2N=.2N=] were investigated using quantum chemistry methods (B3LYP/LANL2DZp). The evaluation of model reaction energy values clearly showed that in the [2=N.2=N.2=N] system, Na+ and K+ ions are best suitable for the cryptand, with a slight preference for K+. The Sr2+ is the best fitting alkaline earth ion, followed by the Ca2+ ion. [2N=.2N=.2N=] clearly prefers the smaller ions. The sodium cation is undoubtedly the favorite, with the potassium ion coming in second. The magnesium ion is the most stable, with the calcium and strontium ions having the next most stable energetic values. The investigation of the M-N bond lengths corroborates the findings of the energetic criteria, confirming the same picture and ion selectivity. These differences in ion selectivity are a result of the differing flexibility of the two cryptands under investigation [2=N.2=N.2=N] and [2N=.2N=.2N=]. The cryptand [2=N.2=N.2=N] optimizes its dihedral angle to host guest cations effectively, while [2N=.2N=.2N=] gains greater flexibility from its C-N … N-C dihedral angle. The greater flexibility of [2N=.2N=.2N=] allows it to form a more suitable cavity to nest the guests due to the different location of the imine double bond in the bridges of the cryptates.
CRIS-Team Scopus Importer:2025-01-31
Keywords: cryptand; DFT; host-guest chemistry; Selective ion complexation

Hydration and water exchange of zinc(II) ions. Application of density functional theory - Hartmann, Michael; Clark, Timothy; van Eldik, Rudi (Journal of the American Chemical Society, 1997)
Details of the hydration and water exchange mechanism of Zn2+ have been studied using density functional calculations with a variety of different basis sets. The computed structures and hydration energies for complexes of the type [Zn(H2O)(n)](2+) with n = 1-6 are in good agreement with previous results obtained from ab initio calculations and self-consistent reaction field methods. Extension of our investigations to the second coordination (first solvation) sphere and thus to complexes of the general type [Zn(H2O)(n)](2+). mH(2)O with n = 5 and m = 1, 2 and n = 6 and m = 1 reveals two types of complexes having either one or two hydrogen bonds between first and second sphere water molecules. The water exchange mechanism of [Zn(H2O)(6)](2+) is analyzed on the basis of the structures and energies of these complexes. Within the variations due to the different basis sets employed, the Zn-O bond length for water molecules in the first coordination sphere is between 2.0 and 2.1 Angstrom, water molecules in the second coordination sphere between 3.6 and 4.1 Angstrom and at the frontier of both spheres between 2.7 and 3.0 Angstrom. Within the limitations of the present model, in which bulk water, counterions, and more than one exchanging water molecule have not been considered, a limiting dissociative (D) mechanism for the water exchange reaction on [Zn(H2O)(6)](2+) is suggested. On the basis of the most reliable structures (i.e., those that could be verified with all levels of theory), the energy of activation for the water exchange is between 4.2 and 4.6 kcal/mol, depending on the basis set employed. A transition state for the interchange mechanism could not be localized. All optimizations invariably led to transition state structures that indicate a limiting D mechanism.

Hydroxychloroquine-Loaded Chitosan Nanoparticles Induce Anticancer Activity in A549 Lung Cancer Cells: Design, BSA Binding, Molecular Docking, Mechanistic, and Biological Evaluation - Elshami, Fawzia I.; Shereef, Hadeer A.; El-Mehasseb, Ibrahim M.; Shaban, Shaban Y.; van Eldik, Rudi (International Journal of Molecular Sciences, 2023)
The current study describes the encapsulation of hydroxychloroquine, widely used in traditional medicine due to its diverse pharmacological and medicinal uses, in chitosan nanoparticles (CNPs). This work aims to combine the HCQ drug with CS NPs to generate a novel nanocomposite with improved characteristics and bioavailability. HCQ@CS NPs are roughly shaped like roadways and have a smooth surface with an average size of 159.3 ± 7.1 nm, a PDI of 0.224 ± 0.101, and a zeta potential of +46.6 ± 0.8 mV. To aid in the development of pharmaceutical systems for use in cancer therapy, the binding mechanism and affinity of the interaction between HCQ and HCQ@CS NPs and BSA were examined using stopped-flow and other spectroscopic approaches, supplemented by molecular docking analysis. HCQ and HCQ@CS NPs binding with BSA is driven by a ground-state complex formation that may be accompanied by a non-radiative energy transfer process, and binding constants indicate that HCQ@CS NPs–BSA was more stable than HCQ–BSA. The stopped-flow analysis demonstrated that, in addition to increasing BSA affinity, the nanoformulation HCQ@CS NPS changes the binding process and may open new routes for interaction. Docking experiments verified the development of the HCQ–BSA complex, with HCQ binding to site I on the BSA structure, primarily with the amino acids, Thr 578, Gln 579, Gln 525, Tyr 400, and Asn 404. Furthermore, the nanoformulation HCQ@CS NPS not only increased cytotoxicity against the A549 lung cancer cell line (IC50 = 28.57 ± 1.72 μg/mL) compared to HCQ (102.21 ± 0.67 μg/mL), but also exhibited higher antibacterial activity against both Gram-positive and Gram-negative bacteria when compared to HCQ and chloramphenicol, which is in agreement with the binding constants. The nanoformulation developed in this study may offer a viable therapy option for A549 lung cancer.
CRIS-Team Scopus Importer:2023-11-10
Keywords: A549 lung cancer; antibacterial; cell penetration; dissociation constants; drug affinity; hydroxychloroquine; molecular docking; nanoparticles

Influence of an extremely negatively charged porphyrin on the reversible binding kinetics of NO to Fe(III) and the subsequent reductive nitrosylation - Jee, Joo-Eun; Eigler, Siegfried; Jux, Norbert; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2007)

Influence of aqueous extracts of urban airborne particulate matter on the structure and function of human serum albumin - Mazuryk, Olga; Gajda-Morszewski, Przemysław; Flejszar, Monika; Łabuz, Przemysław; van Eldik, Rudi; Stochel, Grażyna; Brindell, Małgorzata (Environmental Pollution, 2020)
Human exposure to particulate matter (PM) originating from air pollution is inevitable since more and more population is present in large cities that are characterized by poor air quality. The impact on human health is evident and we need to intensify research regarding this problem to get molecular insight into versatile effects of chronic exposure to PM inducing organism responses and initiating the development of selected disorders. Herein, the impact of standard PM representing urban pollution on the structure and function of human serum albumin (HSA) was evaluated by the application of various analytical techniques. HSA was selected due to its high likeliness of being exposed to PM because of the abundance of this protein in blood. The studies were focused mainly on the inorganic residue of PM resulting from removing organic components by a low-temperature plasma. To mimic physiological conditions, dialysis technique was used to simulate the release of nanoparticles and ions from PM to aqueous environment under, which in turn may interact with biomolecules inside the living system. Capture of metals from the bulk suspension was found for many metals like Al, Fe, Zn and Pb in quantities of more than 1 mol of metal ions per mole of HSA. No significant structural changes of the protein upon dialysis with PM were observed, however, an increase in the thermal stabilization of the HSA structure was observed. Moreover, the interaction of HSA dialyzed in the presence of PM with selected drugs (warfarin, aspirin) was negatively affected, indicating a lower affinity of drugs towards the protein, even though only small conformational changes of the PM exposed protein were observed. Our findings point to a possible interference of air pollutants with the drugs taken by patients living in highly polluted areas.
CRIS-Team Scopus Importer:2020-05-08
Keywords: Conformational changes; Drug binding capacity; Human serum albumin; Inorganic residue of particulate matter; Particulate matter pollution

Influence of chelate effects on the water-exchange mechanism of polyaminecarboxylate complexes of iron(III) - Schneppensieper, Thorsten; Seibig, Sabine; Zahl, Achim; Tregloan, Peter; van Eldik, Rudi (Inorganic Chemistry, 2001)

Influence of modified nano-copper oxide particles on the reaction between nitrocobalamin and ascorbic acid - Polaczek, Justyna; Stochel, Grazyna; Molina, Daniel Ruiz; Vazquez, Fernando Novio; van Eldik, Rudi (Polyhedron, 2022)
CuO nanoparticles have demonstrated a significant effect on the formation kinetics of nitrosylcobalamin (CblNO) in the reaction between nitrocobalamin (CblNO(2)) and ascorbic acid (Asc). Nanoparticles of CuO were modified by coating with a polydopamine layer (nCuO-pDP) and addition of functional ligands (o-(aminoethyl) polyethylene) (nCuO-pDP-polymer). It was demonstrated that the introduction of modifications improved the stability of the suspension and partially eliminated the aggregation of the nanoparticles. Kinetic measurements showed that the modified nanoparticles of CuO clearly accelerate the reaction between nitrocobalamin (CblNO(2)) and ascorbic acid (Asc) under weakly acidic conditions. The presented research is part of the project 'Air Pollution versus Autoimmunity: Role of multiphase aqueous Inorganic Chemistry' that aims at studying the effect of inorganic compounds as a part of particulate matter (PM) on the processes that could affect the course of autoimmune diseases.
CRIS-Team WoS Importer:2022-07-08

Inhaled silica nanoparticles exacerbate atherosclerosis through skewing macrophage polarization towards M1 phenotype - Stachyra, Kamila; Wiśniewska, Anna; Kiepura, Anna; Kuś, Katarzyna; Rolski, Filip; Czepiel, Klaudia; Chmura, Łukasz; Majka, Grzegorz; Surmiak, Marcin; Polaczek, Justyna; van Eldik, Rudi; Suski, Maciej; et al. (Ecotoxicology and Environmental Safety, 2022)
Background and aims: Exposure to environmental nanoparticles is related to the adverse impact on health, including cardiovascular system. Various forms of nanoparticles have been reported to interact with endothelium and induce inflammation. However, the potential role of nanoparticles in the pathogenesis of atherosclerosis and their mechanisms of action are still unclear. The aim of this study was to investigate the effect of two broadly used nanomaterials, which also occur in natural environment - silicon oxide (SiO2) and ferric oxide (Fe2O3) in the form of nanoparticles (NPs) - on the development of atherosclerosis. Methods: We used apolipoprotein E-knockout mice exposed to silica and ferric oxide nanoparticles in a whole body inhalation chamber. Results: Inhaled silica nanoparticles augmented the atherosclerotic lesions and increased the percentage of pro-inflammatory M1 macrophages in both the plaque and the peritoneum in apoE-/- mice. Exposure to ferric oxide nanoparticles did not enhance atherogenesis process, however, it caused significant changes in the atherosclerotic plaque composition (elevated content of CD68-positive macrophages and enlarged necrotic core accompanied by the decreased level of M1 macrophages). Both silica and ferric oxide NPs altered the phenotype of T lymphocytes in the spleen by promoting polarization towards Th17 cells. Conclusions: Exposure to silica and ferric oxide nanoparticles exerts impact on atherosclerosis development and plaque composition. Pro-atherogenic abilities of silica nanoparticles are associated with activation of pro-inflammatory macrophages.
CRIS-Team Scopus Importer:2022-01-07
Keywords: ApoE-knockout mice; Atherosclerosis; Atherosclerotic plaque; Macrophages; Nanoparticles

Inorganic reaction mechanisms. A personal journey - Hubbard, Colin; Chatterjee, Debabrata; Oszajca, Maria; Polaczek, Justyna; Impert, Olga; Chrzanowska, Marta; Katafias, Anna; Puchta, Ralph; van Eldik, Rudi (Dalton Transactions, 2020)
This review covers highlights of the work performed in the van Eldik group on inorganic reaction mechanisms over the past two decades in the form of a personal journey. Topics that are covered include, from NO to HNO chemistry, peroxide activation in model porphyrin and enzymatic systems, the wonder-world of RuIII(edta) chemistry, redox chemistry of Ru(iii) complexes, Ru(ii) polypyridyl complexes and their application, relevant physicochemical properties and reaction mechanisms in ionic liquids, and mechanistic insight from computational chemistry. In each of these sections, typical examples of mechanistic studies are presented in reference to related work reported in the literature.
CRIS-Team Scopus Importer:2020-04-28

Insight into chemically reactive metabolites of aliphatic amine pollutants: A de novo prediction strategy and case study of sertraline - Jin, Lingmin; Cheng, Shiyang; Ding, Wen; Huang, Jingru; van Eldik, Rudi; Ji, Li (Environment International, 2024)
The uncommon metabolic pathways of organic pollutants are easily overlooked, potentially leading to idiosyncratic toxicity. Prediction of their biotransformation associated with the toxic effects is the very purpose that this work focuses, to develop a de novo method to mechanistically predict the reactive toxicity pathways of uncommon metabolites from start aliphatic amine molecules, which employed sertraline triggered by CYP450 enzymes as a model system, as there are growing concerns about the effects on human health posed by antidepressants in the aquatic environment. This de novo prediction strategy combines computational and experimental methods, involving DFT calculations upon sequential growth, in vitro and in vivo assays, dissecting chemically reactive mechanism relevant to toxicity, and rationalizing the fundamental factors. Significantly, desaturation and debenzylation-aromatization as the emerging metabolic pathways of sertraline have been elucidated, with the detection of DNA adducts of oxaziridine metabolite in mice, highlighting the potential reactive toxicity. Molecular orbital analysis supports the reactivity preference for toxicological-relevant C-N desaturation over N-hydroxylation of sertraline, possibly extended to several other aliphatic amines based on the Bell-Evans-Polanyi principle. It was further validated toward some other wide-concerned aliphatic amine pollutants involving atrazine, ε-caprolactam, 6PPD via in silico and in vitro assays, thereby constituting a complete path for de novo prediction from case study to general applications.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Aliphatic Amine Pollutants; C-N desaturation; Chemically Reactive Mechanism; Cytochromes P450; De Novo Prediction; Sertraline

Investigation of the complete encapsulation process of the noble gases by cryptophanes - Ćoćić, Dušan; Yang, Liu; Puchta, Ralph; Shi, Tiesheng; van Eldik, Rudi (Journal of Computational Chemistry, 2024)
Based on DFT calculations (ωB97XD/def2-SVP/SVPfit), the ability and mechanism of noble gas encapsulation by series of cryptophanes were investigated. The focus was set to study the influence of different functionalization groups placed at the “gates” of cryptophanes cavity entrance by which the energy criteria were chosen as a main indicator for selective encapsulation of noble gases. Chosen functionalization groups were -CH3, -OCH3, -OH, -NH2, and -Cl, and the encapsulation process of these cryptophanes was compared to a cryptophane without any functionalization group on its outer rim. Those groups were selected based on their different chemical properties and based on their size which will subsequently put additional steric restrictions on the cavity entrance. Chosen functionalization groups, beside their steric influence on the energy barrier magnitude, influence also the gating process through its chemical nature by which they can put an additional stabilization on noble gases encapsulation transition states enhancing the encapsulation process. Objective of this study was clearly to get better insights on the influence of those functional groups on the whole encapsulation process of noble gases. Large-size noble gases (Xe and Rn) from all noble gases are best accommodated in the cavities of selected cryptophanes, on the other hand these noble gases require to pass the highest energy barrier through the gating process. From the series of investigated cryptophanes, the cryptophane with the -OCH3 functionalization group has been identified as the one with the best capabilities to host investigated noble gases, but on the other side this cryptophane puts the highest energy criteria required for the previous gating process.
CRIS-Team Scopus Importer:2024-11-08
Keywords: cryptophane; DFT; gating process; host-guest chemistry; noble gases

Investigation of the uncatalyzed hydration of CO2 and first approximations to the active site of carbonic anhydrase - A combined Ab initio and DFT study - Hartmann, Michael; Clark, Timothy; van Eldik, Rudi (Journal of Molecular Modeling, 1996)

Investigation of water substitution at Ru-II complexes by conceptual density function theory approach - Cocic, Dusan; Petrovic, Biljana; Puchta, Ralph; Chrzanowska, Marta; Katafias, Anna; van Eldik, Rudi (Journal of Computational Chemistry, 2022)
In this paper, we investigated water exchange reactions and substitution of aqua Ru-II complexes of general formula [Ru(terpy)(N<^>N)(H2O)](2+) (where N<^>N = ethylenediamine (en), 1,2-(aminomethyl)pyridine (ampy) and 2,2 '-bipyridine (bipy)) by ammonia and thioformaldehyde. These reactions were studied in detail by applying conceptual density functional theory. This approach enabled us to gain further insight into the underlying reaction mechanism at the microscopic level (involving only direct participants of the reaction, without the influence of the solvent) and to put the concept of reaction mechanism on a quantitative basis. The course of the chemical reaction along the reaction coordinate xi, is rationalized in terms of reaction energy, force, dipole moment, and reaction electronic flux (REF). The results yield and characterize the significant influence of an intermolecular hydrogen bond formed between the entering and the spectator ligand to the overall energy barrier of the reactions.
CRIS-Team WoS Importer:2022-05-13

Is bis(trifluoromethylsulfonyl)amide an innocent anion? X-ray structure data and DFT calculations. - Illner, Peter; Puchta, Ralph; Heinemann, Frank Wilhelm; van Eldik, Rudi (Dalton Transactions, 2009)
The coordinative behaviour of the bis(trifluoromethylsulfonyl)amide (NTf2-) anion was studied in terms of its interaction with the labile [Pd(terpyridine)Cl]Cl complex. Among various attempts to coordinate NTf2- to the Pd(II) centre, the complexes [Pd(terpyridine)NO3]NTf2 and [Pd(terpyridine)H2O](NTf2)2 were isolated and characterized. The crystallographic data for these complexes are presented and the possible coordination of the NTf2- anion to the metal centre is discussed in reference to DFT predictions.

Kinetic and mechanistic studies on the reaction of nitric oxide with a water-soluble octa-anionic iron(III) porphyrin complex - Eigler, Siegfried; Hampel, Frank; Jux, Norbert; Wolak, Maria; Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 2005)
The polyanionic water-soluble and non-μ-oxo-dimer-forming iron porphyrin iron(III) 5,10,15,20-tetra- tert-butyl-5,5,15,15-tetrakis[2, 2-bis(carboxylato)ethyl]-5,10,15,20-tetraphenylporphyrin, (P) Fe (1), was synthesized as an octasodium salt by applying well-established porphyrin and organic chemistry procedures to bromomethylated precursor porphyrins and characterized by standard techniques such as UV-vis and H NMR spectroscopy. A single pK value of 9.26 was determined for the deprotonation of coordinated water in (P)Fe (HO) (1-H2O) present in aqueous solution at pH <9. The porphyrin complex reversibly binds NO in aqueous solution to give the mononitrosyl adduct, (P)Fe(NO )(L), where L = HO or OH. The kinetics of the binding and release of NO was studied as a function of pH, temperature, and pressure by stopped-flow and laser flash photolysis techniques. The diaqua-ligated form of the porphyrin complex binds and releases NO according to a dissociative interchange mechanism based on the positive values of the activation parameters ΔS and ΔV for the "on" and "off" reactions. The rate constant k = 6.2 × 10 M s (24°C), determined for NO binding to the monohydroxo-ligated (P)Fe(OH) (1-OH) present in solution at pH >9, is markedly lower than the corresponding value measured for 1-HO at lower pH (k = 8.2 × 10 M s , 24°C, pH 7). The observed decrease in the reactivity is contradictory to that expected for the diaqua- and monohydroxo-ligated forms of the iron(III) complex and is accounted for in terms of a mechanistic changeover observed for 1-HO and 1-OH in their reactions with NO. The mechanistic interpretation offered is further substantiated by the results of water-exchange studies performed on the polyanionic porphyrin complex as a function of pH, temperature, and pressure. © 2005 American Chemical Society.

Kinetics and mechanism of the cobalt phthalocyanine catalyzed reduction of nitrite and nitrate by dithionite in aqueous solution - Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 2003)

Kinetics and mechanism of the complexation of La3+ and Cu2+ ions with N-methylacetohydroxamic acid and desferrioxamine B1 - Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 1999)

Kinetics and mechanism of the iron phthalocyanine catalyzed reduction of nitrite by dithionite and sulfoxylate in aqueous solution - Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 2005)
The reactions of sodium nitrite with sodium dithionite and sulfoxylate ion were studied in the presence of iron(III) tetrasulfophthalocyanine, Fe (TSPc), in aqueous alkaline solution. Kinetic parameters for the different reaction steps in the catalytic reduction by dithionite were determined. The final product of the reaction was found to be nitrous oxide. Contrary to this, the product of the catalytic reduction of nitrite by sulfoxylate was found to be ammonia. The striking difference in the reaction products is accounted for in terms of different structures of the intermediate complexes formed during the reduction by dithionite and sulfoxylate, in which nitrite is suggested to coordinate to the iron complex via nitrogen and oxygen, respectively. Sulfoxylate is shown to be a convenient reductant for the synthesis of the highly reduced iron phthalocyanine species Fe(TSPc) in aqueous solution. The kinetics of the reduction of Fe(TSPc) to Fe (TSPc), as well as the oxidation of the latter species by nitrite, was studied in detail. © 2005 American Chemical Society.

Kinetics and mechanism of the reversible binding of nitric oxide to reduced cobalamin B_12r_ - van Eldik, Rudi; Zahl, Achim; et al. (Journal of the American Chemical Society, 2001)
The reduced form of aquacobalamin binds nitric oxide very effectively to yield a nitrosyl adduct, Cbl(II)-NO. UV-vis, 1H-, 31P-, and 15N NMR data suggest that the reaction product under physiological conditions is a six-coordinate, "base-on" form of the vitamin with a weakly bound α-dimethylbenzimidazole base and a bent nitrosyl coordinated to cobalt at the β-site of the corrin ring. The nitrosyl adduct can formally be described as Cbl(III)-NO-. The kinetics of the binding and dissociation reactions was investigated by laser flash photolysis and stopped-flow techniques, respectively. The activation parameters, ΔH‡, ΔS‡, and ΔV‡, for the forward and reverse reactions were estimated from the effect of temperature and pressure on the kinetics of these reactions. For the "on" reaction of Cbl(II) with NO, the small positive ΔS‡ and ΔV‡ values suggest the operation of a dissociative interchange (Id) substitution mechanism at the Co(II) center. Detailed laser flash photolysis and 17O NMR studies provide evidence for the formation of water-bound intermediates in the laser flash experiments and strongly support the proposed Id mechanism. The kinetics of the "off" reaction was studied using an NO-trapping technique. The respective activation parameters are also consistent with a dissociative interchange mechanis
UnivIS-Import:2015-03-09:Pub.2001.forsch.sonder.sfb583.kineti

Kinetics and mechanism of the reversible binding of nitric oxide to reduced cobalamin B12r (Cob(II)alamin) - Wolak, Maria; Zahl, Achim; Schneppensieper, Thorsten; Stochel, Grażyna; van Eldik, Rudi (Journal of the American Chemical Society, 2001)

Kinetics, mechanism and density functional theory calculations on base hydrolysis of α-amino acid esters catalyzed by [Pd(AEMP)(H2O)2]2+ (AEMP = 2-(2-aminoethyl)-1-methylpyrrolidine) - Shoukry, Mohamed M.; Shehata, Mohamed R.; Ragab, Mona S.; Ćorćić, Dušan; Puchta, Ralph; van Eldik, Rudi (Reaction Kinetics Mechanisms and Catalysis, 2020)
Abstract: Pd(AEMP)Cl2 (AEMP = 2-(2-aminoethyl)-1-methylpyrrolidine) was synthesized and characterized by spectral and thermal measurements.[Pd(AEMP)(H2O)2]2+ reacts with amino acid esters (L) to form mixed ligand [Pd(AEMP)L]2+ complexes. The kinetics of the base hydrolysis of [Pd(AEMP)L]2+ was studied by a pH-stat technique and the corresponding rate constants are reported. The coordinated glycine methyl ester is hydrolyzed efficiently, whereas the coordinated methionine- and histidine- methyl esters undergo hydrolysis with a much lower catalytic activity. The catalytic effect is controlled by the mode of coordination of the ester to the Pd(II) complex. Possible mechanisms for these reactions are considered. Activation parameters were determined experimentally for the hydrolysis of the coordinated glycine methyl ester. DFT calculations (B3LYP/def2svp) were applied to gain further insight into the possible mechanism of the base hydrolysis of the amino acid esters. The calculations are discussed in reference to the reported experimental data. Graphic abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-02-25
Keywords: 2-(2-Aminoethyl)-1-methylpyrrolidine; Amino acid ester; Catalytic hydrolysis; DFT calculations; Pd(II); pH-stat technique

Ligand-exchange processes on solvated lithium cations: Acetonitrile and hydrogen cyanide - Pasgreta, Ewa; Puchta, Ralph; Zahl, Achim; van Eldik, Rudi (European Journal of Inorganic Chemistry, 2007)
Solutions of LiClO in solvent mixtures of acetonitrile and water, or acetonitrile and nitromethane, were studied by Li NMR spectroscopy. Measured chemical shifts indicate that the Li cation is coordinated by four acetonitrile molecules. In the binary water/acetonitrile mixture, water coordinates more strongly to Li than acetonitrile such that addition of writer immediately leads to the formation of [Li(H O)]. The solvent-exchange mechanism for [Li(L)] (L = CHCN and HCN) was studied by using DFT calculations (RB3LYP/6-311+G* *). This process was found to follow a limiting associative mechanism involving the formation of relatively stable five-coordinate intermediates. The suggested mechanisms are discussed with reference to available experimental and theoretical data. © Wiley-VCH Verlag GmbH & Co. KGaA, 2007.

Ligand exchange processes on solvated lithium cations: Complexation by cryptands in acetone as solvent - Pasgreta, Ewa; Puchta, Ralph; Zahl, Achim; van Eldik, Rudi (European Journal of Inorganic Chemistry, 2007)
Keywords: Cryptands; Acetone; Lithium; Exchange mechanism

Ligand exchange processes on solvated lithium cations: Complexation by cryptands in acetone as solvent - Pasgreta, Ewa; Puchta, Ralph; Zahl, Achim; van Eldik, Rudi (European Journal of Inorganic Chemistry, 2007)
Kinetic studies on Li exchange between the cryptands C222 and C221 and acetone as solvent were performed as a function of ligand-to-metal ratio, temperature and pressure using Li NMR spectroscopy. Temperature and pressure dependence measurements were performed in the presence of an excess of Li. The rate and activation parameters for the exchange process are: C222: k = (1.7 ± 0.5) × 10 s, ΔH = 24 ± 1 kJ mol and ΔS# = -105 ± 4 J K mol; C221: k = 2.24 ± 0.09 s, ΔH# = 29 ± 2 kJ mol and ΔS# = -141 ± 5 J K mol. The influence of pressure on the exchange rate is insignificant for both ligands, such that the activation volume is around zero within the experimental error limits. The reported activation parameters suggest that the exchange of Li between solvated and chelated ions follows an associative interchange mechanism. © Wiley-VCH Verlag GmbH & Co. KGaA, 2007.

Ligand-exchange processes on solvated lithium cations: DMSO and water/DMSO mixtures - Pasgreta, Ewa; Puchta, Ralph; Galle, Michael; van Eikema Hommes, Nico; Zahl, Achim; van Eldik, Rudi (ChemPhysChem, 2007)
Solutions of LiClO in solvent mixtures consisting of dimethylsulfoxide (DMSO) and water, or DMSO and γ-butyrolactone, were studied by Li NMR spectroscopy (for complexation by cryptands in γ-butyrolactone as a solvent, see: E. Pasgreta, R. Puchta, M. Galle, N. J. R. van Eikema Hommes, A. Zahl, R. van Eldik, J. Incl. Phen., 2007, 58, 81-88). Chemical shifts indicate that the Li ion is coordinated by four DMSO molecules. In the binary solvent mixture of water and DMSO, no selective solvation is detected, thus indicating that on increasing the water content of the solvent mixture, DMSO is gradually displaced by water in the coordination sphere of Li. The ligand-exchange mechanism of Li ions solvated by DMSO and water/DMSO mixtures was studied using DFT calculations. Ligand exchange on [Li(DMSO)] was found to follow a limiting associative (A) mechanism. The displacement of coordinated H O by DMSO in [Li(HO)] follows an associative interchange mechanism. The suggested mechanisms are discussed in reference to available experimental and theoretical data. © 2007 Wiley-VCH Verlag GmbH & Co. KGaA.

Ligand Exchange Processes on Solvated Lithium Cations. II. Complexation by Cryptands in γ-Butyrolactone as Solvent - Pasgreta, Ewa; Puchta, Ralph; Galle, Michael; van Eikema Hommes, Nico; Zahl, Achim; van Eldik, Rudi (Journal of Inclusion Phenomena and Macrocyclic Chemistry, 2007)
Kinetic studies on Li exchange between the cryptands C222 and C221, and γ-butyrolactone as solvent were performed as a function of ligand-to-metal ratio, temperature and pressure using Li NMR. The thermal rate and activation parameters are: C222: k = (3.3 ± 0.8)×10 M s, ΔH = 35 ± 1 kJ mol and ΔS = -41 ± 3 J K mol; C221: k = 105 ± 32 M s, ΔH = 48 ± 1kJ mol and ΔS = -45 ± 2 J K mol. Temperature and pressure dependence measurements were performed in the presence of an excess of Li. The influence of pressure on the exchange rate is insignificant for both ligands, such that the value of activation volume is around zero within the experimental error limits. The activation parameters obtained in this study indicate that the exchange of Li between solvated and chelated Li ions follows an associative interchange mechanism. © Springer Science+Business Media B.V. 2007.
Keywords: gamma-butyrolactone; cryptands; exchange mechanism; Lithium

Ligand exchange processes on solvated lithium cations. VI. Determination of coordination numbers by ligand substitution and 7Li NMR - Schmeißer, Matthias; Zahl, Achim; Scheurer, Andreas; Puchta, Ralph; van Eldik, Rudi (Journal of the American Chemical Society, 2010)
On the basis of 7Li NMR studies the coordination mode of phenantroline (phen) and bipyridine (bipy) to Li+ ions was found to be [Li(phen)2]+ and [Li(bipy)2]+ in the weakly coordinating solvent nitromethane. A large chemical shift of the 7Li signal indicated a strong interaction between the ligand and the metal center. The related sp2-hybridized N-donor ligand 2, 2′-bis[(4S)-4-benzyl-2-oxazoline] (biox) showed a negligible effect on the 7Li shift, suggesting that almost no interaction occurs between the Li+ center and biox as compared to Li+ and the solvent γ-butyrolactone. Corresponding DFT (RB3LYP/LANL2DZp) calculations have clearly indicated that the poor coordination of biox is not caused by steric effects but rather by the electronic nature of the heterocyclic biox system. © 2010 Verlag der Zeitschrift für Naturforschung.
UnivIS-Import:2015-10-26:Pub.2010.nat.dchph.laoc1.ligand
Keywords: DFT calculations; Lithium complex formation; N chelates

Ligand‐tuning of the stability of pd(Ii) conjugates with cyanocobalamin - Porębska, Dominika; Orzeł, Łukasz; Rutkowska‐zbik, Dorota; Stochel, Grażyna; van Eldik, Rudi (International Journal of Molecular Sciences, 2021)
Besides the well‐known functions performed by vitamin B12 (CblCN) in biochemical processes of the human body, an increasing interest has been raised by the possibility of its use as a transmembrane drug carrier, capable, among others, of enhancing the accumulation of inorganic cytostatics in cancer cells. The present study was aimed at determining the possibility of the formation of CblCN conjugates with Pd(II) complexes. A key aspect was their stability, which we attempted to tune by appropriate choice of ligands. Syntheses, spectroscopic analysis of postreaction systems and kinetic investigations of conjugate formation reactions, have been complemented by DFT modelling. The obtained results showed that ligand charge, geometry and electron affinity may have a significant impact on carrier binding and release leading to the activation of the Pd(II) complex. This provides a rationale to expect that with appropriate composition of the coordination sphere, it will be possible to extend the spectrum of less toxic inorganic chemotherapeutics.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Complex stability; Cyanocobalamin; Drug delivery systems; Palladium(II) complexes

Local dense structural heterogeneities in liquid water from ambient to 300 MPa pressure: Evidence for multiple liquid-liquid transitions - Khoshtariya, Dimitri E.; Zahl, Achim; Dolidze, Tina D.; Neubrand, Anton; van Eldik, Rudi (ChemPhysChem, 2004)

Mechanism of water exchange on five-coordinate copper(II) complexes - Neubrand, Anton; Thaler, Florian; Körner, Manuela; Zahl, Achim; van Eldik, Rudi; et al. (Journal of the Chemical Society, Dalton Transactions, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.laoc1.mechan

Mechanistic details of the catalytic degradation of methylene blue by hydrogen peroxide in basic solution. The unexpected innocence of percarbonate - Trocha, Aniela; Impert, Olga; Katafias, Anna; van Eldik, Rudi (Polyhedron, 2021)
Recently it was shown that the Mn-III(TPPS) - hydrogen peroxide system in alkaline media exhibits a vigorous catalase activity. Intermediate (TPPS)Mn-V = O formed in a catalytic cycle in the system is an efficient degrading agent for a model dye, Orange II, in carbonate buffers. The high efficacy of the catalyst under these conditions is attributed to the generation of strongly oxidising percarbonate ions, a commonly known effect. The detailed study on the Mn-III(TPPS) catalysed rapid degradation of methylene blue by hydrogen peroxide, performed using stopped-flow electronic spectroscopy as a function of the catalyst, hydrogen peroxide, pH and carbonate con-centrations reported herein, has surprisingly evidenced a minor role of percarbonate in the overall catalytic cycle.
CRIS-Team WoS Importer:2021-12-03

Mechanistic information from low-temperature rapid-scan and NMR measurements on the protonation and subsequent reductive elimination reaction of a (diimine)platinum(II) dimethyl complex - Wik, Bror J.; Ivanovic-Burmazovic, Ivana; Tilset, M.; van Eldik, Rudi (Inorganic Chemistry, 2006)
A detailed kinetic study of the protonation and subsequent reductive elimination reaction of a (diimine)platinum(II) dimethyl complex was undertaken in dichloromethane over the temperature range of -90 to +10°C by stopped-flow techniques. Time-resolved UV-vis monitoring of the reaction allowed the assessment of the effects of acid concentration, coordinating solvent (MeCN) concentration, temperature, and pressure. The second-order rate constant for the protonation step was determined to be 15200 ± 400 M s at -78°C, and the corresponding activation parameters are ΔH = 15.2 ± 0.6 kJ mol and ΔS = -85 ± 3 J mol K, which are in agreement with the addition of a proton that results in the formation of the platinum(IV) hydrido complex. The kinetics of the second, methane-releasing reaction step do not show an acid dependence, and the MeCN concentration also does not significantly affect the reaction rate. The activation parameters for the second reaction step were found to be ΔH = 75 ± 1 kJ mol, ΔS = +38 ± 5 J mol K, and ΔV = +18 ± 1 cm mol, strongly suggesting a dissociative character of the rate-determining step for the reductive elimination reaction. The spectroscopic and kinetic observations were correlated with NMR data and assisted the elucidation of the underlying reaction mechanism. © 2006 American Chemical Society.

Mechanistic information from volume profiles for water exchange and complex-formation reactions of aquated Ni(II). pH, buffer and medium effects - Gazzaz, Hanaa Asaad; Ember, Erika; Zahl, Achim; van Eldik, Rudi (Dalton Transactions, 2009)
Rate and activation parameters for the complex-formation reaction of Ni with 4-(2-pyridylazo)-N,N-dimethyl aniline (PADA) were studied as a function of pH in different buffers in both aqueous and sodium dodecyl sulfate (SDS) micelle solutions. In aqueous Tris buffer solution, the forward and backward rate constants increased with increasing pH, while the complex-formation constant decreased due to a larger increase in the backward rate constant. The activation entropy, ΔS, and activation volume, ΔV, changed with increasing pH from positive to negative values, suggesting an apparent changeover from a dissociative to a more associative mechanism. Complex-formation reactions with 2,2′-bipyridine in Tris buffer showed almost no increase in the forward and backward rate constants on increasing the pH, but the ΔS and ΔV values became more negative. N-ethylmorpholine buffer showed no pH effect on the rate constants and activation parameters. Water exchange reactions of aquated Ni were also studied as a function of pH under the same conditions. The reported rate and activation parameters for water exchange in Tris and N-ethylmorpholine buffers are consistent with those found for the complex-formation reactions of Ni with PADA. The observed pH and buffer effects for both the complex-formation and water exchange reactions of aquated Ni can be accounted for in terms of the formation of a Ni-Tris complex in Tris buffer and general base catalysis by the buffer components. In SDS micelle solution, the complex-formation reaction with PADA was much faster than in aqueous solution, but the increase in rate constant with increasing pH was less significant, while ΔS and ΔV became more positive, pointing to a more dissociative mechanism. For SDS micelle solutions there was no effect on the water exchange rate constant or activation volume. Mechanistic interpretations are offered for all observed pH, buffer and medium effects. © The Royal Society of Chemistry 2009.

Mechanistic information on the reductive elimination from cationic trimethylplatinum(IV) complexes to form carbon-carbon bonds - Zahl, Achim; van Eldik, Rudi; Liehr, Günter; et al. (Inorganic Chemistry, 2005)
Cationic complexes of the type fac-[(L)PtMe (pyr-X)][OTf] (pyr-X = 4-substituted pyridines; L = diphosphine, viz., dppe = bis(diphenylphosphino)ethane and dppbz = o-bis(diphenylphosphino)benzene; OTf = trifluoromethane-sulfonate) undergo C-C reductive elimination reactions to form [LPtMe(pyr-X)] [OTf] and ethane. Detailed studies indicate that these reactions proceed by a two-step pathway, viz., initial reversible dissociation of the pyridine ligand from the cationic complex to generate a five-coordinate Pt intermediate, followed by irreversible concerted C-C bond formation. The reaction is inhibited by pyridine. The highly positive values for ΔS = +180 ± 30 J K mol , ΔH = 160 ± 10 kJ mol, and ΔV = +16 ± 1 cm mol can be accounted for in terms of significant bond cleavage and/or partial reduction from Pt to Pt in going from the ground to the transition state. These cationic complexes have provided the first opportunity to carry out detailed studies of C-C reductive elimination from cationic Pt complexes in a variety of solvents. The absence of a significant solvent effect for this reaction provides strong evidence that the C-C reductive coupling occurs from an unsaturated five-coordinate Pt intermediate rather than from a six-coordinate Pt solvento species. © 2005 American Chemical Society.

Mechanistic insight on the chemistry of potential Pt antitumor agents as revealed by collaborative research performed in Kragujevac and Erlangen - Petrović, Biljana; Jovanović, Snezana; Puchta, Ralph; van Eldik, Rudi (Inorganica Chimica Acta, 2019)
This personal account reports on the mechanistic insight gained on the chemistry of potential Pt antitumor agents based on the collaborative research between the groups of Živadin Bugarčić in Kragujevac (Serbia) and Rudi van Eldik in Erlangen (Germany). The work focuses on different mononuclear Pt(II) and Pt(IV), as well as dinuclear Pt(II) complexes, the tuning of their lability through steric and electronic (σ-donor and π-acceptor) effects, their interaction with sulfur- and nitrogen-donor bio-relevant nucleophiles, the elucidation of structure-reactivity relationships, and DFT calculations on ground, transition and product state complexes. It presents an overview of the investigated systems and reveals mechanistic information on the basis of spectroscopic and kinetic measurements.
CRIS-Team Scopus Importer:2019-06-21
Keywords: DFT calculations; Di-nuclear Pt(II) complexes; Kinetics; Mechanism; Pt(II) complexes; Pt(IV) complexes

Mechanistic insight on the water exchange mechanism of [Zn(tren)H2O](2+) and related complexes from a DFT study - Alzoubi, Basam; Cocic, Dusan; Puchta, Ralph; van Eldik, Rudi (Journal of Coordination Chemistry, 2022)
The mechanisms for water exchange on [Zn(L)H2O](2+)center dot H2O (L = tren: tris(2-aminoethypamine, trep: tris(2-phosphinoethyl)phosphine, and tres: tris(2-arsinoethyl)arsine) were studied using density functional theory (B3LYP/6-311+G**) and evaluated by MP2 and B3LYP(PCM) energy calculations. The activation barriers for the water exchange reaction on [Zn(L)H2O](2+)center dot H2O (L = tren, trep and tres) are (B3LYP/6-311 - G**) 9.9, 10.13 and 11.23 kcal mol(-1), respectively. Topological analyses of the investigated ground state complexes were performed. The energy and structural data support an associative interchange (I-a) water exchange pathway.
CRIS-Team WoS Importer:2022-05-13

Mechanistic studies on a facile ring-flipping process in planar chiral ferrocenes under ambient and high pressure and its relevance to asymmetric catalysis - Zahl, Achim; van Eldik, Rudi; et al. (Organometallics, 2004)

Mechanistic studies on the formation of Pt(II) hydroformylation catalysts in imidazolium-based ionic liquids - Illner, Peter; Zahl, Achim; Puchta, Ralph; van Eikema Hommes, Nico; Wasserscheid, Peter; van Eldik, Rudi (Journal of Organometallic Chemistry, 2005)
The kinetics of the formation of the active species cis-[Pt (PPh)Cl(SnCl)] and cis-[Pt (PPh)(SnCl)] from the hydroformylation catalyst precursor cis-[Pt(PPh )Cl] in the presence of SnCl, was studied in two different imidazolium-based ionic liquids. A large range of different chlorostannate melts consisting of 1-butyl-3-methyl-imidazolium cations and [SnCl] anions with varying molar fraction of SnCl, were prepared and characterized by H and Sn NMR. The observed chemical shifts point to major changes in the composition of the anionic species within the melt. The second ionic liquid employed, viz., 1-butyl-3-methyl-imidazolium-bis(trifluormethylsulfonyl)amide was prepared in a colorless quality that enabled its application in kinetic studies. The concentration and temperature dependence of the substitution of Cl by [SnCl] to yield cis-[Pt(PPh )Cl(SnCl)], could be studied in detail. Theoretical (DFT) calculations were employed to model the reaction progress and to resolve the role of the ionic liquid in the activation of the catalyst. The available results are presented and a plausible mechanism for the formation of the catalytically active species is suggested. © 2005 Elsevier B.V. All rights reserved.

Mechanistic Studies on the Reaction between Aquacobalamin and the HNO Donor Piloty's Acid over a Wide pH Range in Aqueous Solution - Polaczek, Justyna; Subedi, Harishchandra; Orzeł, Łukasz; Lisboa, Lynn S.; Cink, Ruth B.; Stochel, Grażyna; Brasch, Nicola E.; van Eldik, Rudi (Inorganic Chemistry, 2021)
Detailed kinetic and mechanistic studies have been carried out on the reaction between aquacobalamin/hydroxocobalamin (CblOH2+/CblOH) and nitroxyl (HNO) generated by Piloty's acid (PA, N-hydroxybenzenesulfonamide) over a wide pH range (3.5-13). The resulting data showed that in a basic solution HNO can react with hydroxocobalamin to form nitrosylcobalamin despite the inert nature of CblOH. It was shown that at low PA concentrations the rate-determining step is the decomposition of PhSO2NHO- to release HNO, whereas the reaction between CblOH and HNO becomes the rate-determining step at high PA concentrations. Data from kinetic studies on the reaction of CblOH with an excess of HNO enabled us to experimentally determine the pKa(HNO) value from initial rate data as a function of pH, giving pKa(HNO) = 11.47 ± 0.04. An especially interesting observation was made in the neutral pH range, where PA is stable and does not produce HNO. Under such conditions, rapid formation of CblNO was observed in the studied system. The obtained data suggest that CblOH2+ reacts directly with PA to form a Piloty's acid-bound cobalamin intermediate, which deprotonates rapidly at neutral pH followed by rate-determining S-N bond cleavage to give CblNO and release PhSO2-.
CRIS-Team Scopus Importer:2021-02-26

Mechanistic Studies on the Reaction of [FeIII(edta)(H2O)]– with Piloty′s Acid as Source for HNO - Muthig, André; Polaczek, Justyna; van Eldik, Rudi (European Journal of Inorganic Chemistry, 2019)
In earlier work performed in our laboratories, the reaction of [FeII(edta)(H2O)]2– with ·NO(g) was studied as a trap for ·NO(g) and found to be very efficient with a formation constant of ca. 106 M–1 at 25 °C. The formed nitrosyl complex was shown to have substantial FeIII-NO–, i.e. nitroxyl, character in line with detailed computational studies performed before. In recent years, we developed an interest in the chemistry of HNO/NO– (nitroxyl) and decided to use [FeIII(edta)(H2O)]– as starting material to see whether the reaction of this complex would lead directly to the formation of the nitroxyl complex by using a source for HNO. In the present study, Piloty's acid (benzenesulfonylhydroxamic acid) was used as source for HNO, since it cleanly hydrolysis in basic aqueous solution to release HNO. The results of our studies clearly indicate that the same reaction product as found for the reaction of [FeII(edta)(H2O)]2– with ·NO(g), was formed in the reaction of [FeIII(edta)(H2O)]– with Piloty's acid. A detailed spectroscopic and mechanistic study of the latter reaction is reported.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Iron; Piloty's acid; Radicals; Reaction mechanisms

Mechanistic studies on the reductive elimination of methane from methyl(hydrido)platinum(IV) complexes - Fekl, Ulrich; Zahl, Achim; van Eldik, Rudi (ACS National Meeting Book of Abstracts, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.laoc1.mechan_8

Metabolic response of raw 264.7 macrophages to exposure to crude particulate matter and a reduced content of organic matter - Jankowska-Kieltyka, Monika; Roman, Adam; Mikrut, Magdalena; Kowalska, Marta; van Eldik, Rudi; Nalepa, Irena (Toxics, 2021)
Exposure to air pollution from various airborne particulate matter (PM) is regarded as a potential health risk. Airborne PM penetrates the lungs, where it is taken up by macrophages, what results in macrophage activation and can potentially lead to negative consequences for the organism. In the present study, we assessed the effects of direct exposure of RAW 264.7 macrophages to crude PM (NIST1648a) and to a reduced content of organic matter (LAp120) for up to 72 h on selected parameters of metabolic activity. These included cell viability and apoptosis, metabolic activity and cell number, ROS synthesis, nitric oxide (NO) release, and oxidative burst. The results indicated that both NIST1648a and LAp120 negatively influenced the parameters of cell viability and metabolic activity due to increased ROS synthesis. The negative effect of PM was concentration-dependent; i.e., it was the most pronounced for the highest concentration applied. The impact of PM also depended on the time of exposure, so at respective time points, PM induced different effects. There were also differences in the impact of NIST1648a and LAp120 on almost all parameters tested. The negative effect of LAp120 was more pronounced, what appeared to be associated with an increased content of metals.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Cell viability; Nitric oxide; Particulate matter; Reactive oxygen species

Metal complex-assisted activation of small molecules. from NO to superoxide and peroxides - Ivanovic-Burmazovic, Ivana; van Eldik, Rudi (Dalton Transactions, 2008)
Transition metal centres are one of the primary targets for nitric oxide (NO), superoxide (Ȯ) and hydrogen peroxide (H O), which are small molecules present in a biological milieu, and of industrial and environmental interest. Coordination to a metal centre modulates their redox behaviour in such a way that they become activated for an inner-sphere oxidation or reduction, depending on the electronic and redox properties of a particular transition metal ion. Since the related redox reactions play multiple roles in physiological and pathophysiological processes, as well as in chemical catalysis in terms of synthetic applications and exhaust gas purification, the elucidation of the mechanisms of the elementary reaction steps behind these complex processes is of fundamental importance. This review concentrates on our work in this area, where by applying low temperature and high pressure kinetic and thermodynamic techniques we shed more light on the mechanisms of the particular reaction steps involved in the activation of NO, Ȯ and various peroxides. The studies include work on solvent exchange reactions that control the binding of small molecules to the metal centre and subsequent electron-transfer processes. We paid special attention to different iron and manganese complexes with heme and non-heme ligand systems. © The Royal Society of Chemistry.

Microstructure, Physical and Biological Properties, and BSA Binding Investigation of Electrospun Nanofibers Made of Poly(AA-co-ACMO) Copolymer and Polyurethane - Mansour, Hanaa; Elsigeny, Samia M.; Elshami, Fawzia I.; Auf, Mohamed; Shaban, Shaban Y.; van Eldik, Rudi (Molecules, 2023)
In this study, poly(AA-co-ACMO) and polyurethane-based nanofibers were prepared in a ratio of 1:1 (NF11) and 2:1 (NF21) as antimicrobial carriers for chronic wound management. Different techniques were used to characterize the nanofibers, and poly(AA-co-ACMO) was mostly found on the surface of PU. With an increase in poly(AA-co-ACMO) dose from 0 (PU) and 1:1 (NF11) to 2:1 (NF21) in the casting solution, the contact angle (CA) was reduced from 137 and 95 to 24, respectively, and hydrophilicity was significantly increased. As most medications inhibit biological processes by binding to a specific protein, in vitro protein binding was investigated mechanistically using a stopped-flow technique. Both NF11 and NF21 bind to BSA via two reversible steps: a fast second-order binding followed by a slow first-order one. The overall parameters for NF11 (Ka = 1.1 × 104 M−1, Kd = 89.0 × 10−6, ΔG0 = −23.1 kJ mol−1) and NF21 (Ka = 189.0 × 104 M−1, Kd = 5.3 × 10−6 M, ΔG0 = −27.5 kJ mol−1) were determined and showed that the affinity for BSA is approximately (NF11)/(NF21) = 1/180. This indicates that NF21 has much higher BSA affinity than NF11, although BSA interacts with NF11 much faster. NF21 with higher hydrophilicity showed effective antibacterial properties compared to NF11, in agreement with kinetic data. The study provided an approach to manage chronic wounds and treating protein-containing wastewater.
CRIS-Team Scopus Importer:2023-05-26
Keywords: antibacterial; BSA-affinity; electrospun; hydrophilic; nanofiber; poly(acrylic acid-co-acryloylmorpholine); wound healing

Molecular orbital and DFT studies on water exchange mechanisms of metal ions - van Eldik, Rudi; Clark, Timothy; Hanauer, Hans (Coordination Chemistry Reviews, 2003)
An overview of recent molecular orbital theory and density functional theory studies on water exchange reactions of metal ions and complexes in solution is presented. The different theoretical techniques used are reviewed and representative examples are discussed. The mechanistic insight gained is discussed in reference to available experimental data and the predictive nature of the applied techniques is highlighted. © 2002 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.forsch.sonder.sfb583.molecu
Keywords: DFT studies; Molecular orbital; Water exchange mechanisms

Molecular Parameters Promoting High Relaxivity in Cluster-Nanocarrier Magnetic Resonance Imaging Contrast Agents - Lyons, Trevor; Kekedjian, Chloe; Glaser, Priscilla; Ohlin, C. André; van Eldik, Rudi; Rodriguez, Olga; Albanese, Christopher; Van Keuren, Edward; Stoll, Sarah L. (ACS Applied Materials and Interfaces, 2022)
We have investigated the mechanism of relaxivity for two magnetic resonance imaging contrast agents that both employ a cluster-nanocarrier design. The first system termed Mn8Fe4-coPS comprises the cluster Mn8Fe4O12(L)16(H2O)4or Mn8Fe4(1) (L = carboxylate) co-polymerized with polystyrene to form ∼75 nm nanobeads. The second system termed Mn3Bpy-PAm used the cluster Mn3(O2CCH3)6(Bpy)2or Mn3Bpy (2) where Bpy = 2,2′-bipyridine, entrapped in ∼180 nm polyacrylamide nanobeads. Here, we investigate the rate of water exchange of the two clusters, and corresponding cluster-nanocarriers, in order to elucidate the mechanism of relaxivity in the cluster-nanocarrier. Swift-Connick analysis of O-17 NMR was used to determine the water exchange rates of the clusters and cluster-nanocarriers. We found distinct differences in the water exchange rate between Mn8Fe4and Mn8Fe4-coPS, and we utilized these differences to elucidate the nanobead structure. Using the transverse relaxivity from O-17 NMR line widths, we were able to determine the hydration state of the Mn3Bpy (2) cluster as well as Mn3Bpy-PAm. Using these hydration states in the Swift-Connick analysis of O-17 NMR, we found the water exchange rate to be extremely close in value for the cluster Mn3Bpy and cluster-nanocarrier Mn3Bpy-PAm.
CRIS-Team Scopus Importer:2022-11-11
Keywords: MRI contrast agent; nanobead; O-17 NMR; relaxivity; water exchange

Nanoscale Coordination Chemistry - Ruiz-Molina, Daniel; van Eldik, Rudi (Advances in Inorganic Chemistry, 2020)
CRIS-Team WoS Importer:2021-02-19

Nitrosyl- versus nitroxyl-cobalamin? - Polaczek, Justyna; Orzel, Lukasz; Stochel, Grazyna; van Eldik, Rudi (Journal of Biological Inorganic Chemistry, 2019)
The Commentary is in answer to the comment of a reader that objected against the use of the term ‘nitroxylcobalamin’ in two recent reports in JBC from our group. We use this opportunity to explain to the reader where this terminology originated from.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Cobalamin; Metal porphyrins; Nitric oxide; Nitrosyl; Nitroxyl; Non-heme complexes

NO Binding to Cobalamin: Influence of the Metal Oxidation State - van Eldik, Rudi; Clark, Timothy; et al. (Inorganic Chemistry, 2004)
Density functional and molecular orbital theory calculations on models for cobalamin suggest that NO binds similarly to the Co(II) and Co(III) oxidation states. However, Co(III) can bind water far more strongly than Co(II) as a sixth ligand, so that the competition between water and NO complexation strongly favors water for Co(III) in the gas phase. Although the Co(II) oxidation state is found to bind water slightly more strongly than NO in the gas phase, the inclusion of solvation effects via the polarizeable continuum model makes NO binding more favorable. Thus, the experimentally observed ability of cob(II)alamin to bind NO in aqueous solution is the result of its weak complexation with water and the relatively poor solvation of NO. Calculated vibrational frequencies support the interpretation of the cob(II)alamin-NO complex as being cob(III)alamin-NO-, although the DFT calculations underestimate the degree of charge transfer in comparison to Hartree-Fock calculations.
UnivIS-Import:2015-03-09:Pub.2004.forsch.sonder.sfb583.nobind

Noble guests in organic cages–encapsulation of noble gases by cryptophane - Ćoćić, Dušan; Puchta, Ralph; van Eldik, Rudi (Journal of Coordination Chemistry, 2020)
With the application of DFT calculations (ωB97XD/def2-SVP/SVPfit), the ability and mechanism of noble gas encapsulation by cryptophane was investigated. Based on the applied model reaction, by monitoring geometric changes and investigating the non-covalent interactions between the studied hosts and the noble gases, the size of the host did not necessarily play a decisive role in the selective encapsulation of the guests. Rather the adjustment of the host’s interior and functionalization of its “gates” can be significant in tuning the affinity of cryptophanes.
CRIS-Team Scopus Importer:2020-10-02
Keywords: cryptophane; DFT; host-guest chemistry; Noble gases

Oxidation of hydroxyurea with oxovanadium(V) ions in acidic aqueous solution - Zahl, Achim; van Eldik, Rudi; et al. (Journal of Inorganic Biochemistry, 2006)
Hydroxyurea (HU) effectively reduces vanadium(V) into vanadium(IV) species (hereafter V and V species, respectively) in acidic aqueous solution via the formation of a transient complex followed by an electron transfer process that includes the formation and subsequent fading out of a free radical, U (U ≡ H N-C(=O)N(H)O ). The electron paramagnetic resonance (EPR) spectra of U in H O/D O solutions suggest that the unpaired electron is located predominantly on the hydroxamate hydroxyl-oxygen atom. Visible and V -EPR spectroscopic data reveal HU as a two-electron donor, whereas formation of U , which reduces a second V , indicates that electron transfer occurs in two successive one-electron steps. At the molarity ratio [V ]/[HU] = 2, the studied reaction can be formulated as: 2 V + HU → 2 V + 0.98 CO + 0.44 N O + 1.1 NH + 0.1 NH OH. Lack of evidence for the formation of NO is suggested to be a consequence of the slow oxidation of HNO due to the too low reduction potential of the V /V couple under the experimental conditions used. The nuclear magnetic resonance ( V-NMR) spectral data indicate protonation of (H O) V O , and the protonation equilibrium constant was determined to be K = 0.7 M . Spectrophotometric titration data for the V -HU system reveal formation of (H O) V O(OH)U and (H O) V OU . Their stability constants were calculated as K = 5 M and K = 22 M , where the subscript digits refer to (H O) V O , HU and H , respectively. © 2006 Elsevier Inc. All rights reserved.

Oxidoreductase mimicking activity of Ru(edta) complexes in conversion of NAD coenzymes - Chrzanowska, Marta; Katafias, Anna; van Eldik, Rudi; Chatterjee, Debabrata (Polyhedron, 2022)
The realization of the reversible inter-conversion between NAD+ and NADH (Scheme 1) is a long-term challenge in biological and energy-related chemistry. Potential of Ru(edta) complexes mimicking oxidoreductase enzymes in the redox conversion of NAD coenzymes has been explored in the present work. The oxidation of NADH to NAD+ by [RuIII(edta)(pz)]- (edta4- = ethylenediaminetetraacetate; pz = pyrazine) has been studied spectrophotometrically and kinetically in aqueous solution at pH 7.0 (mes buffer) as a function of [NADH] and temperature. A working mechanism for the [RuIII(edta)(pz)]- complex mediated redox conversion of NAD coenzymes has been proposed. A mechanism in agreement with the kinetic data and activation parameters is presented.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Electron transfer; NAD Coenzymes; Reaction mechanism; Redox reactions; Ru(edta)

Physicochemical analysis of water extracts of particulate matter from polluted air in the area of kraków, poland - Mikrut, Magdalena; Macyk, Wojciech; van Eldik, Rudi; Stochel, Grażyna (Atmosphere, 2021)
Solubility of transition metal compounds plays a significant role in adverse health effects because that is one of the most important factors of particulate matter bioavailability in the body. In this study, we focus on the chemical analysis of particulate matter (PM) collected at different locations in the area of Kraków, one of the most polluted cities in Poland, and compare them with Standard Reference Material (SRM) 1648a from NIST. The content of four elements (carbon, hydrogen, nitrogen, and sulfur) was determined by elemental analysis, and the ratio between organic and inorganic carbon in PM extracts was confirmed by Total Organic Carbon analysis. Among the most concentrated elements found there are calcium, magnesium, sulfur, silicon, and zinc, whereas copper, iron, and manganese were present in lower concentrations. SEM-EDS analysis showed a similar morphology of the SRM and PM collected in the urban area of Kraków, while PM collected in the industrial area has smaller particles with a smooth surface. The reported analyses are significant for the APARIC project (“Air Pollution versus Autoimmunity: Role of multiphase aqueous Inorganic Chemistry”), which aims to identify the main inorganic components of PM and to understand how they affect the development of immunological diseases.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Air pollution; Particulate matter; Reactive oxygen species; Redox-active metal ions

Prediction of ion selectivity by quantum chemical calculations X: A recent (personal) review - Puchta, Ralph; Begel, Svetlana; van Eldik, Rudi (Computational Chemistry, 2019)
In this review we present a simple and robust method to investigate the ion selectivity of cryptands based on quantum chemical methods. Based on easily understandable model equations and fundamental structural consideration one can rationalize or predict the observed selectivity and the underlying structural conditions. Additionally, we can learn unhampered from neighboring effects the changes in the cryptand to host the ions most effectively. The performance of this concept is demonstrated on several well known cryptands from different supramolecular groups like Lehn and others.
CRIS-Team Scopus Importer:2019-08-23
Keywords: DFT; Main group ions; Selective ion complexation; 2-Cryptands

Preface - van Eldik, Rudi; Ivanovic-Burmazovic, Ivana (Academic Press, Inc., 2012)

Probing the interaction of iron complex containing N3S2 macrocyclic ligand with bovine serum albumin using spectroscopic techniques - El-Shamy, Hany; Shaban, Shaban Y.; El-Mehasseb, Ibrahim; El-Kemary, Maged; van Eldik, Rudi (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2019)
The interaction of bovine serum albumin (BSA) with seven-coordination iron (II) complex containing sulfur-based macrocyclic ligand was investigated by means of UV/vis absorption spectroscopy and fluorescence quenching technique. The accurate fluorescence spectra are obtained by using Inner filter effect (IFE) correction. The apparent association constant, kapp, the number of binding sites, n, and the apparent binding constant KSV were found to be 0.95 × 103 M− 1, 0.96, and 6.13 × 104 M−1, respectively. It found that BSA molecules are adsorbed on the surface of iron (II) complex by electrostatic interaction. The quenching mechanism is discussed involving energy transfer from BSA to iron (II) complex.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Bovine serum albumin; Energy transfer; Fluorescence quenching; Inner filter effect; Iron (II) complex; Macrocyclic ligand

(untitled)
The enantiomerisation pathway for [Pt(thiourea)4]F+ [a model for the C-4-symmetric [Pt(SU)(4)]SiF6 (SU = thiourea) complex] and derivatives is explored by density functional theory (B3LYP/LANL2DZp) and the activation barrier for the one-step process from C-4 to C-4' via a C-4 transition state is computed. The substitution of Pt2+ by Pd2+ and Ni2+ and the exchange of selenourea and tellurourea increase the barrier. (([[Pt(thiourea)(4)]

Rational design of cation hosts - Prediction of cation selectivity by quantum chemical calculations - Galle, Michael; Puchta, Ralph; van Eikema Hommes, Nico; van Eldik, Rudi (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2006)
Structures of [M subset of 2.2.2](n+) obtained with MNDO, AM1, PM3, PM3/SPASS, and PM5, are evaluated against X-ray and DFT (B3LYP/LANL2DZp) geometries. DFT and X-ray structures agree well, followed by PM3/SPASS. The ion selectivity calculated with DFT and PM3/SPASS for a simple model reaction, agrees satisfactorily with the available complex-formation constants (log K-S). The applied theoretical treatment has a good predictive potential.
Keywords: DFT; semi-empirical; sparkle; host-guest; cation selectivity

Reaction mechanisms relevant to the formation and utilization of [Ru(edta)(NO)] complexes in aqueous media - Chatterjee, Debabrata; Chrzanowska, Marta; Katafias, Anna; van Eldik, Rudi (Journal of Inorganic Biochemistry, 2021)
The advancement of Ru(edta) complexes (edta4− = ethylenediamineteraacetate) mediated reactions, including NO generation and its utilization, has not been systematically reviewed to date. This review aims to report the research progress that has been made in exploring the application of Ru(edta) complexes in trapping and generation of NO. Furthermore, utilization of the potential of Ru(edta) complexes to mimic NO synthase and nitrite reductase activity, including thermodynamics and kinetics of NO binding to Ru(edta) complexes, their NO scavenging (in vitro), and antitumor activity will be discussed. Also, the role of [Ru(edta)(NO)] in mediating electrochemical reduction of nitrite, S-nitrosylation of biological thiols, and cross-talk between NO and H2S, will be covered. Reports on the NO-related chemistry of Fe(edta) complexes showing similar behavior are contextualized in this review for comparison purposes. The research contributions compiled herein will provide in-depth mechanistic knowledge for understanding the diverse routes pertaining to the formation of the [Ru(edta)(NO)] species, and its role in effecting the aforementioned reactions of biochemical significance.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Mechanistic issues; NO binding; NO release; Ru(edta); S-nitrosylation; Therapeutic application

Reaction of [Ru-III(EDTA)(H2O/OH)](?/2?) with bisulfide and persulfide in aqueous solution: kinetic and mechanistic studies - Oszajca, Maria; Chatterjee, Debabrata; van Eldik, Rudi (Journal of Coordination Chemistry, 2019)
The reaction of [Ru-III(EDTA)(H2O/OH)](?)(/2)(?) (EDTA(4?) = ethylenediaminetetraacetate) with bisulfide (HS?) and persulfide (HSS?) leading to the formation of a dinuclear disulfur-bridged [(EDTA)(RuSSRuIII)-S-III(EDTA)](4?) product has been studied spectrophotometrically. Kinetics of the reaction of [Ru-III(EDTA)(H2O/OH)](?)(/2)(?) with HS? was studied in aqueous solution as a function of [HS-] at a constant pH of 8.2 (phosphate buffer) and temperature (20??C). Formation of the product complex, [(EDTA)(RuSSRuIII)-S-III(EDTA)](4?), in the reaction of [Ru-III(EDTA)(H2O/OH)](?)(/2)(?) with HSS? was identified by ESI-MS studies. A working mechanism in agreement with the spectroscopic and kinetic data is presented.
CRIS-Team WoS Importer:2019-11-15

Recent Highlights II Preface - van Eldik, Rudi; Hubbard, Colin D. (Advances in Inorganic Chemistry, 2022)
CRIS-Team WoS Importer:2022-11-18

Reduction pathway of end-on terminally coordinated dinitrogen. V. N-N bond cleavage in Mo/W hydrazidium complexes with diphosphine coligands. Comparison with triamidoamine systems - Mersmann, Klaus; Horn, Kay H.; Böres, Natascha; Lehnert, Nicolai; Studt, Felix; Paulat, Florian; Peters, Gerhard; Ivanovic-Burmazovic, Ivana; van Eldik, Rudi; Tuczek, Felix (Inorganic Chemistry, 2005)
N-N cleavage of the dialkylhydrazido complex [W(dppe)(NNC H)] (B) upon treatment with acid, leading to the nitrido/imido complex and piperidine, is investigated experimentally and theoretically. In acetonitrile and at room temperature, B reacts orders of magnitude more rapidly with HNEtBPh than its Mo analogue, [Mo(dppe)-(NNCH)] (B ). A stopped-flow experiment performed for the reaction of B with HNEtBPh in propionitrile at -70°C indicates that protonation of B is completed within the dead time of the stopped-flow apparatus, leading to the primary protonated intermediate BH. Propionitrile coordination to this species proceeds with a rate constant K of 1.5 ± 0.4 s, generating intermediate RCN-BH (R = Et) that rapidly adds a further proton at N and then mediates N-N bond splitting in a slower reaction (K = 0.35 ± 0.08 s, 6 equiv of acid). K and K are found to be independent of the acid concentration. The experimentally observed reactivities of B or B with acids in nitrile solvents are reproduced by DFT calculations. In particular, geometry optimization of models of solvent-coordinated, N-protonated intermediates is found to lead spontaneously to separation into the nitrido/imido complexes and piperidine/piperidinium, corresponding to activationless heterolytic N-N bond cleavage processes. Moreover, DFT indicates a spontaneous cleavage of nonsolvated B protonated at N. In the second part of this article, a theoretical analysis of the N-N cleavage reaction in the Mo(III) triamidoamine complex [HIPTNN]Mo(N) is presented (HIPTNN = hexaisopropylterphenyltriamidoamine). To this end, DFT calculations of the MoN triamidoamine complex and its protonated and reduced derivatives are performed. Calculated structural and spectroscopic parameters are compared to available experimental data. N-N cleavage most likely proceeds by one-electron reduction of the Mo(V) hydrazidium intermediate [HIPTNN]Mo(NNH), which is predicted to have an extremely elongated N-N bond. From an electronic-structure point of view, this reaction is analogous to that of Mo/W hydrazidium complexes with diphos coligands. The general implications of these results with respect to synthetic N fixation are discussed. © 2005 American Chemical Society.

Reply to the Comment on the Article "Gutmann Donor and Acceptor Numbers for Ionic Liquids" (Chem. Eur. J. 2012, 18, 10969-10982) by J.-F. Gal and C. Laurence - Schmeißer, Matthias; Illner, Peter; Puchta, Ralph; Zahl, Achim; van Eldik, Rudi (Chemistry - A European Journal, 2013)

Revealing a nonergodic mechanistic pattern for electron exchange between azurin and electrodes coated by nano-films under the glassy environmental conditions - Dolidze, Tinatin; van Eldik, Rudi; Khoshtariya, Dimitri (Bulletin of the Georgian National Academy of Sciences, 2019)
Fast-scan protein-film voltammetry was applied to explore interfacial biomimetic electron exchange under the environmental glass forming conditions. Gold electrodes were coated with 1-pentanethiol SAM–azurin (Az, blue cupredoxin) assemblies and placed in contact with a water-doped and buffered protic ionic melts of choline dihydrogen phosphate ([ch][dhp]), served as electrolyte media, allowing for a necessary cell conductivity under the virtually solid, semi-solid and liquid electrolyte conditions over 273–353 K, within which the electron exchange rate was studied as a function of the water amount and temperature. Exposure of the Az films to the semi-solid electrolyte greatly affected the protein’s conformational dynamics, hence the ET rate, via the mechanism occurring in the extra complicated dynamically-controlled regime. Results are compared to the earlier studies on the reference system with a conventional electrolyte, allowing for the disclosure of mutually-entangled mechanistic motifs. Under the “standard” condition (with no [ch][dhp] added), the Az biomolecule may reside in an apparently ergodic state, whereas upon adding of [ch][dhp] to allow water content ranging between 6 to 15 waters per [ch][dhp], system displays anomalous temperature dependences, suggesting that the reactive system crosses a broad, well-manifested nonergodic zone which arises from the continuous interplay (freezing/unfreezing) of ET-coupled highly cooperative conformational modes of the Az protein, inherently linked to the electrolyte’s slowest collective relaxation(s). Above this [ch][dhp] concentration, allowing the water content between 1.65 to 3.7 waters per ion pair, the system returns to a series of new, quasi-ergodic states, with each displaying virtually linear Arrhenius patterns yet with distinct parameters.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Electron exchange; Interphase; Nonergodicity; Redox protein; Self assembly

Role of π-acceptor effects in controlling the lability of novel monofunctional Pt(II) and Pd(II) complexes: Crystal structure of [Pt(tripyridinedimethane)Cl]Cl - Petrovic, Biljana; Bugarcic, Zivadin D.; Dees, Anne; Ivanovic-Burmazovic, Ivana; Heinemann, Frank Wilhelm; Puchta, Ralph; Steinmann, Stephan N.; Corminboeul, Clemence; van Eldik, Rudi (Inorganic Chemistry, 2012)
The kinetics and mechanism of substitution reactions of novel monofunctional [Pt(tpdm)Cl] and [Pd(tpdm)Cl] complexes (where tpdm = tripyridinedimethane) and their aqua analogues with thiourea (tu), l-methionine (l-met), glutathione (GSH), and guanosine-5′-monophosphate (5′-GMP) were studied in 0.1 M NaClO at pH = 2.5 (in the presence of 10 mM NaCl for reactions of the chlorido complexes). The reactivity of the investigated nucleophiles follows the order tu > l-met > GSH > 5′-GMP. The reported rate constants showed the higher reactivity of the Pd(II) complexes as well as the higher reactivity of the aqua complex than the corresponding chlorido complex. The negative values reported for the activation entropy as well as the activation volume confirmed an associative substitution mode. In addition, the molecular and crystal structure of [Pt(tpdm)Cl]Cl was determined by X-ray crystallography. The compound crystallizes in a monoclinic space group C2/c with two independent molecules of the complex and unit cell dimensions of a = 38.303(2) Å, b = 9.2555(5) Å, c = 27.586(2) Å, β = 133.573(1)°, and V = 7058.3(8) Å . The cationic complex [Pt(tpdm)Cl] exhibits square-planar coordination around the Pt(II) center. The lability of the [Pt(tpdm)Cl] complex is orders of magnitude lower than that of [Pt(terpyridine)Cl] . Quantum chemical calculations were performed on the [Pt(tpdm)Cl] and [Pt(terpyridine)Cl] complexes and their reactions with thiourea. Theoretical computations for the corresponding Ni(II) complexes clearly demonstrated that π-back-bonding properties of the terpyridine chelate can account for acceleration of the nucleophilic substitution process as compared to the tpdm chelate, where introduction of two methylene groups prevents such an effective π-back bonding. © 2012 American Chemical Society.

RuIII(edta) complexes as molecular redox catalysts in chemical and electrochemical reduction of dioxygen and hydrogen peroxide: inner-sphereversusouter-sphere mechanism - Chatterjee, Debabrata; Chrzanowska, Marta; Katafias, Anna; Oszajca, Maria; van Eldik, Rudi (RSC Advances, 2021)
The reduction of molecular oxygen (O2) and hydrogen peroxide (H2O2) by [RuII(edta)(pz)]2−(edta4−= ethylenediaminetetraacetate; pz = pyrazine) has been studied spectrophotometrically and kinetically in aqueous solution. Exposure of the aqua-analogue [RuII(edta)(H2O)]2−to O2and H2O2resulted in the formation of [RuIII(edta)(H2O)]−species, with subsequent formation of the corresponding RuVO complex. A working mechanism for the O2and H2O2reduction reactions mediated by the RuII(edta) complexes is proposed. The role of the coordinated water molecule (by its absence or presence in the primary coordination sphere) in controlling the mechanistic pathways, outer-sphere or inner-sphere, is discussed.
CRIS-Team Scopus Importer:2021-07-23

RuIII(edta)-mediated interaction of nitrite and sulphide: Formation of an N-bonded thionitrous acid (HSNO) complex of RuIII(edta) in aqueous solution - Chatterjee, Debabrata; Chowdhury, Chandra; Datta, Ayan; van Eldik, Rudi (New Journal of Chemistry, 2019)
The nitrite anion (NO2-) is an important source of nitric oxide (NO) or nitrosonium cations (NO+). In the present study, we have shown that [RuIII(edta)(NO+)] (edta4- = ethylendiaminetetraacetate) generated via decomposition of [RuIII(edta)(NO2)]2- at lower pH (3.5) could react with H2S to form a putative thionitrous acid (HSNO) bound Ru(edta) complex in aqueous solution. The reaction product [RuIII(edta)(NOSH)]- was characterized by IR, EPR and ESI-MS spectroscopy. Formation of N-coordinated [RuIII(edta)(NOSH)]- was further corroborated by DFT calculations.
CRIS-Team Scopus Importer:2019-10-11

Searching for stable, five-coordinate aquated Al(III) species. Water exchange mechanism and effect of pH - Hanauer, Hans; Puchta, Ralph; Clark, Timothy; van Eldik, Rudi (Inorganic Chemistry, 2007)
Density functional theory calculations have been performed for the water exchange mechanism of aquated Al(III). The effect of pH was considered by studying the exchange processes for [Al(H2O)(6)](3+) and its conjugated base, [Al(H2O)(5)OH](2+). Both complexes were found to exchange water in a dissociative way with activation energies (E-A) of 15.9 and 10.2 kcal/mol, respectively. The influence of solvent molecules on the gas-phase cluster model was considered by the addition of up to four water molecules to the model system. The stabilizing effect of the solvent on the transition state decreases E-A to 8.6 (hexa-aqua complex) and 7.6 (monohydroxo complex) kcal/mol, whereas E-A for all hydroxo species is consistently significantly lower than those for the related aqua systems, which indicates a much faster water exchange rate. For the hydroxo complex, all calculated five-coordinate intermediates, nH(2)O center dot[Al(H2O)(4)(OH)](2+) (n = 1, 2, 3, 4, 5), are more stable than the corresponding six-coordinate reactants. Our results therefore suggest the presence of a stable five-coordinate species of aquated Al(III), namely, the [Al(H2O)(4)(OH)](2+) complex.

Selective Noble Gas Inclusion in Pentagon-Dodecahedral X20-Cages † - Weinert, Christopher; Ćoćić, Dušan; Puchta, Ralph; van Eldik, Rudi (Molecules, 2023)
Using DFT-based computational chemistry calculations (ωB97XD/def2-tzvp//ωB97XD/def2-svp/svpfit + ZPE(ωB97XD/def2-svp/svpfit)), binding energies of noble gases encapsulated in a series of dodecahedrane molecules (general formula: X20H20 where X = C, Si, Ge, Sn and Pb, and X20 where X = N, P, As, Sb and Bi) were calculated to learn about the noble gas selectivity. Based on calculated binding energies, the Sn20H20 cage can best accommodate noble gases with a medium size radius (Ar and Kr), while the Pb20H20 dodecahedrane cage is best suited for noble gases with the larger radii (Xe and Rn). On the other hand, from the elements of the V main group of the periodic table, the Bi20 cage has shown the best results to selectively encapsulate Ar and Kr, with the amounts of energy being released being −5.24 kcal/mol and −6.13 kcal/mol, respectively. By monitoring the geometric changes of all here-reported host cages upon encapsulating the noble gas guest, the host has shown minor to no flexibility, testifying to the high rigidity of the dodecahedrane structure which was further reflected in very high encapsulating energies.
CRIS-Team Scopus Importer:2023-08-25
Keywords: DFT; dodecahedrane; host-guest chemistry; noble gases

Self-exchange reaction kinetics of metallocenes revisited: Insights from the decamethylferricenium-decamethylferrocene reaction at variable pressure - Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 2003)

Seven-coordinate iron(II) complexes of sulfur-based N3S2-macrocyclic ligands: synthesis, properties, and crystal structure - Shaban, Shaban Abd El Fattah Youssef; Ibrahim, Mohamed M.; Heinemann, Frank Wilhelm; van Eldik, Rudi (Journal of Coordination Chemistry, 2012)
The reaction of pyridine-2,6-dicarbaldehyde or 2,6-diacetylpyridine with 1,2-bis(o-aminophenylthio) ethane (1) in acetonitrile in the presence of stoichiometric amounts of iron(II) perchlorate gave the complexes [(pyN(3)S(2))Fe-II(ClO4)(2)] (4) and [(pyN(3)Me(2)S(2)) Fe-II(ClO4)(2)] (5) of the 15-membered N3S2 macrocyclic ligands, pyN(3)S(2) = 6,7-dihydro-15,19-nitrilobenzo( e,p)(1,4,7,15)dithiadiazacyclo-heptadecine-N, N', N '', S, S' and pyN(3)Me(2)S(2) = 6,7-dihydro- 16,18-dimethyl-15,19-nitrilobenzo(e,p)(1,4,7,15)dithiadiazacyclo-heptadecine-N, N', N '', S, S', respectively. Physical measurements led to the conclusion that these complexes contained seven-coordinate iron(II) and a single-crystal X-ray examination of 4 confirmed this. Coordination of the Fe(II) center in 4 is best described as distorted pentagonal-bipyramidal with the three nitrogen atoms and two sulfur donors of the macrocycle defining the pentagonal plane and the perchlorate ions occupying axial positions. Room temperature (293 K) magnetic moments of 4 and 5 (mu(eff) = 4.9 and 4.7 B.M., respectively) are close to the value predicted for high-spin d(6) systems.
Keywords: Iron(II) complexes; Seven-coordinate; Macrocyclic ligands; Pentagonal-bipyramidal

Solvation Largely Accounts for the Effect of N-Alkylation on the Properties of Nickel(II/I) and Chromium(III/II) Cyclam Complexes - Clark, Timothy; Hennemann, Matthias; van Eldik, Rudi; et al. (Inorganic Chemistry, 2002)
The source of the effect of N-alkylation on the redox properties of Ni(II/I) and Cr(III/II) cyclam complexes has been investigated using DFT calculations. The structures of the anhydrous and hydrated complexes were optimized in the gas phase, and single point calculations were performed in a polarized continuum. The main results are the following: the decrease in outer sphere solvation upon N-alkylation is the major source of the relative stabilization of the lower oxidation state complexes by the tertiary amine ligands; tertiary amine nitrogen donors are stronger σ-donors than the secondary amines, as predicted from the inductive effect of alkyls; steric strain elongates the metal-nitrogen bonds in the tertiary complexes and decreases the ligand strain energies; and the site of water binding to the complexes differs because of their different electronic structures (i.e., in the Ni complexes, the water molecules bind to the M-N-H sites, whereas in the Cr complexes they bind to the central metal cation). Outer sphere hydrogen bonding of water to the ligands in the coordination sphere lowers the ionization potentials by charge delocalization.
UnivIS-Import:2015-03-09:Pub.2002.forsch.sonder.sfb583.solvat

Solvent and pressure effects on the motions of encapsulated guests: Tuning the flexibility of a supramolecular host - Mugridge, J.S.; Zahl, Achim; van Eldik, Rudi; Bergmann, R.G.; Raymond, Kenneth (Journal of the American Chemical Society, 2013)

Solvent, salt and high pressure effects on the rate and equilibrium constants for the formation of tri-n-butylphosphoniumdithiocarboxylate - Iskhakova, Gulnara G.; Kiselev, Vladimir D.; van Eldik, Rudi; Zahl, Achim; Shihab, Mehdi S.; Konovalov, Alexander I. (Journal of Physical Organic Chemistry, 2011)
Solvent, salt and high pressure effects on the rate and equilibrium constants for the formation of tri-n-butylphosphoniumdithiocarboxylate at 298.2 K are reported. This equilibrium is shifted to the phosphobetaine in polar solvents, salt solutions and under high external pressure. The reaction volume changes dramatically on going from less polar diethyl ether (-69 cm mol) and tetrahydrofurane (THF) (-66 cm mol ), to more polar acetonitrile (-39 cm mol) and acetone (-38 cm mol). Copyright © 2010 John Wiley & Sons, Ltd.

Solvent tuning of the substitution behavior of a seven-coordinate iron(III) complex - Ivanovic-Burmazovic, Ivana; Hamza, Mohamed; van Eldik, Rudi (Inorganic Chemistry, 2006)
A detailed kinetic study of the substitution behavior of the seven-coordinate [Fe(dapsox)(L)]ClO complex (H -dapsox = 2,6-diacetylpyridine-bis(semioxamazide), L = solvent or its deprotonated form) with thiocyanate as a function of the thiocyanate concentration, temperature, and pressure was undertaken in protic (EtOH and acidified EtOH and MeOH) and aprotic (DMSO) organic solvents. The lability and substitution mechanism depend strongly on the selected solvent (i.e., on solvolytic and protolytic processes). In the case of alcoholic solutions, substitution of both solvent molecules by thiocyanate could be observed, whereas in DMSO only one substitution step occurred. For both substitution steps, [Fe(dapsox)(L)]ClO shows similar mechanistic behavior in methanol and ethanol, which is best reflected by the values of the activation volumes (MeOH ΔV = +15.0 ± 0.3 cm mol, ΔV = +12.0 ± 0.2 cm mol; EtOH ΔV = +15.8 ± 0.7 cm mol, ΔV = +11.1 ± 0.5 cm mol ). On the basis of the reported activation parameters, a dissociative (D) mechanism for the first substitution step and a D or dissociative interchange (I) mechanism for the second substitution step are suggested for the reaction in MeOH and EtOH. This is consistent with the predominant existence of alcoxo [Fe(dapsox)(ROH)(OR)] species in alcoholic solutions. In comparison, the activation parameters for the substitution of the aqua-hydroxo [Fe(dapsox)(HO)(OH)] complex by thiocyanate at pH 5.1 in MES were determined to be ΔH = 72 ± 3 kJ mol , ΔS = +38 ± 11 J K mol, and ΔV = -3.0 ± 0.1 cm mol, and the operation of a dissociative interchange mechanism was suggested, taking the effect of pressure on the employed buffer into account. The addition of triflic acid to the alcoholic solutions ([HOTf] = 10 and 10 M to MeOH and EtOH, respectively) resulted in a drastic changeover in mechanism for the first substitution step, for which an associative interchange (I) mechanism is suggested, on the basis of the activation parameters obtained for both the forward and reverse reactions and the corresponding volume profile. The second substitution step remained to proceed through an I or D mechanism (acidified MeOH ΔV = +9.2 ± 0.2 cm mol ; acidified EtOH ΔV = +10.2 ± 0.2 cm mol). The first substitution reaction in DMSO was found to be slowed by several orders of magnitude and to follow an associative interchange mechanism (ΔS = -50 ± 9 J K mol, ΔV = -1.0 ± 0.5 cm mol), making DMSO a suitable solvent for monitoring substitution processes that are extremely fast in aqueous solution. © 2006 American Chemical Society.

Square planar versus square pyramidal copper(II) complexes containing N3O moiety: Synthesis, structural characterization, kinetic and catalytic mimicking activity - Shaban, Shaban Y.; Ramadan, Abd El-Motaleb M.; Ibrahim, Mohamed M.; Elshami, Fawzya; van Eldik, Rudi (Inorganica Chimica Acta, 2019)
In quest of copper complexes having [CuN3O] cores, [Cu(phen)(L–Val)(H2O)]NO3 (1) and [Cu(bpy)(L–Val)]ClO4 (2) complexes have been synthesized and structurally characterized (phen = 1,10–phenanthroline; bpy = 2,2′–bipyridine). Complex 1 possesses a distorted square-pyramidal, whereas 2 has a distorted square-planar coordination geometry. Structures of 1 and 2 have supramolecular networks formed via inter- and intra-molecular hydrogen bonding interactions. The kinetics and mechanism of ligand substitution of 1 and 2 by thiourea (TU) were studied in detail and showed a biphasic process in which an initial fast reaction is followed by a slower one. The activation parameters for the fast reaction: ΔH# = 68 ± 4 and 73 ± 5 kJ mol−1, ΔS# = 43 ± 10 and 54 ± 9 J K−1 mol−1 for 1 and 2, respectively, supports a dissociative substitution mechanism. Whereas for the slow reaction: ΔH# = 33 ± 6 and 43 ± 3 kJ mol−1, ΔS# = −77 ± 10 and −56 ± 9 J K−1 mol−1 for 1 and 2, respectively, support an associative substitution mechanism. It is concluded from the activation parameters that the difference in structure does not affect the mechanism. Complexes 1 and 2 have also been evaluated as functional models for the catechol oxidase enzyme and phenoxazinone synthase. The model complexes 1 and 2 show catecholase activity of Kcat = 10.9 × 103 and 11.4 × 103 h−1 and phenoxazinone synthase activity of Kcat = 2.1 × 103 and 4.3 × 103 h−1, respectively. Compared to the enzyme itself (Kcat = 8.3 h−1), the model complexes 1 and 2 are promising candidates as functional mimics for catechol oxidase and phenoxazinone synthase.
CRIS-Team Scopus Importer:2019-08-20
Keywords: 1; 10–Phenanthroline; 2; 2′–Bipyridine; Catalytic promiscuity; Catechol oxidase; Copper(II) complex; Crystal structure; L–Valinate; Phenoxazinone synthase

Steric and electronic tuning of the reactivity of [RuII(terpy)(N^N)Cl]Cl complexes - Chrzanowska, Marta; Katafias, Anna; Kozakiewicz, Anna; van Eldik, Rudi (Inorganica Chimica Acta, 2020)
The substitution behavior of [RuII(terpy)(phen)Cl]Cl and [RuII(terpy)(tmen)Cl]ClO4 (where terpy = 2,2′:6′,2″-terpyridine, phen = 1,10-phennatroline, tmen = N,N,N′,N′-tetramethylethylenediamine) have been investigated. The crystal structures of the complexes were determined by single crystal X-ray diffraction. The structures of the complexes in solution were confirmed by ESI-MS and multinuclear NMR spectroscopy. The stability of [RuII(terpy)(phen)Cl]+ and [RuII(terpy)(tmen)Cl]+ in aqueous solution, acidity and substitution behavior of the corresponding aqua derivatives with chloride, thiourea and N,N′-dimethylthiourea, were studied. The kinetics of the substitution reactions was followed under pseudo-first order conditions using UV–visible spectroscopy as a function of nucleophile concentration and temperature. The reactivity and pKa values of the tmen and phen complexes were compared with the earlier studied Ru(II) polypyridine complexes. The aqueous behavior of all the examined Ru(II) complexes depends on the electronic and steric properties provided by the spectator bidentate ligands.
CRIS-Team Scopus Importer:2020-02-11

Structural and Kinetic Studies on the Formation of Platinum(II) and Palladium(II) Complexes with L-Cysteine-Derived Ligands - Rau, Tobias; Alsfasser, Ralf; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 1998)

Structural, spectroscopic, and kinetic investigation of the molybdenum dialkylhydrazido complexes [MoBr(NNC5H10)(dppe) 2]Br and [Mo(NNC5H10)(dppe)2]: Activation parameters and revised mechanism for N-N cleavage - Dreher, Ameli; Mersmann, Klaus; Näther, Christian; Ivanovic-Burmazovic, Ivana; van Eldik, Rudi; Tuczek, Felix (Inorganic Chemistry, 2009)
The reaction of [Mo(NNCH)(dppe)] (B) with an excess of acid, HNEtBPh, is investigated applying temperature-dependent stopped-flow measurements. The kinetic data indicate a biphasic process with rate constants k and K which are both slower than the single rate constant reported by Henderson et al. (Henderson, R. A.; Leigh, G. J.; Pickett, C. J., J, Chem. Soc., Dalton Trans. 1989, 425-430). Moreover, both rate constants exhibit a linear dependence on the acid concentration with a large intercept which is attributed to acid-dependent and acid-independent components of each reaction phase, respectively. All four reaction channels exhibit temperature-dependent reaction rates. Furthermore, B and its Mo(IV) analogue [MoBr(NNCH)(dppe)]Br (A) are characterized structurally and spectroscopically. Density-functional theory calculations are performed to locate possible barriers in the overall reaction scheme and determine their energies, providing additional information for the formulation of a mechanism. The temperature-dependent rate of N-N cleavage is explained by a revised mechanism which involves an α-protonated intermediate that is inert with respect to N-N cleavage and is generated from its β-protonated counterpart by a rapid 1,2-proton shift. The implications of these results with respect to N reduction in the Chatt cycle and the enzyme nitrogenase are discussed. © 2009 American Chemical Society.

Structure and reactivity of [Ru-II(terpy)(NN)Cl]Cl complexes: consequences for biological applications - Chrzanowska, Marta; Katafias, Anna; Impert, Olga; Kozakiewicz, Anna; Surdykowski, Andrzey; Brzozowsk, Paulina; Franke, Alicja; Zahl, Achim; Puchta, Ralph; van Eldik, Rudi (Dalton Transactions, 2017)
The crystal structures of [Ru-II(terpy)(bipy)Cl]Cl center dot 2H(2)O and [Ru-II(terpy)(en) Cl]Cl center dot 3H(2)O, where terpy = 2,2':6',2 ''-terpyridine, bipy = 2,2'-bipyridine and en = ethylenediamine, were determined and compared to the structure of the complexes in solution obtained by multi-nuclear NMR spectroscopy in DMSOd-6 as a solvent. In aqueous solution, both chlorido complexes aquate fully to the corresponding aqua complexes, viz. [Ru-II(terpy)(bipy)(H2O)](2+) and [Ru-II(terpy)(en)(H2O)](2+), within ca. 2 h and ca. 2 min at 37 degrees C, respectively. The spontaneous aquation reactions can only be suppressed by chloride concentrations as high as 2 to 4 M, i.e. concentrations much higher than that found in human blood. The corresponding aqua complexes are characterized by pK(a) values of ca. 10 and 11, respectively, which suggest a more labile coordinated water molecule in the case of the [Ru-II(terpy)(en)(H2O)](2+) complex. Substitution reactions of the aqua complexes with chloride, cyanide and thiourea show that the [Ru-II(terpy)(en)(H2O)](2+) complex is 30-60 times more labile than the [Ru-II(terpy)(bipy)(H2O)](2+) complex at 25 degrees C. Water exchange reactions for both complexes were studied by O-17-NMR and DFT calculations (B3LYP(CPCM)/def2tzvp//B3LYP/def2svp and omega B97XD(CPCM)/def2tzvp//B3LYP/def2svp). Thermal and pressure activation parameters for the water exchange and ligand substitution reactions support the operation of an associative interchange (I-a) process. The difference in reactivity between these complexes can be accounted for in terms of pi-back bonding effects of the terpy and bipy ligands and steric hindrance on the bipy complex. Consequences for eventual biological application of the chlorido complexes are discussed.

Structures of Carbonato and Bicarbonato Complexes of Bis(1,10-phenanthroline)Zinc(II): Experiment and Theory - Hanauer, Hans; Liehr, Günter; Clark, Timothy; van Eldik, Rudi; et al. (European Journal of Inorganic Chemistry, 2003)
We report experimental and theoretical studies on the structure and properties of carbonato and bicarbonato complexes of bis(1,10-phenanthroline)zinc(II). The complex [Zn(phen)2-O2CO] has been synthesized and DFT calculations have been performed based upon its X-ray structure. The carbonate ligand coordinates in a bidentate binding mode to the metal centre with Zn-O distances of 2.130 and 2.092 Å in the X-ray structure and 2.027 Å for both distances in the calculated gas-phase structure. Because of the fundamental role of (bicarbonato)ZnII complexes, especially in different carbonic anhydrases, the structures and properties of the experimentally unknown bicarbonato complexes of this kind were investigated using DFT with different basis sets up to the Ahlrichs triple zeta basis set with additional polarization functions. The bidentate bicarbonato complex [Zn(phen)2O2C(OH)]+ was found to be about 8.2 kcal·mol-1 (SHAsvp), 6.4 kcal·mol-1 (Ahlrichs triple zeta with polarization functions) and 3.5 kcal·mol-1 (Ahlrichs triple zeta) more stable than the quasi-monodentate bicarbonato complex [Zn(phen)20(OH)CO]+. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2003).
UnivIS-Import:2015-03-09:Pub.2003.forsch.sonder.sfb583.struct
Keywords: Bicarbonate complexes; Carbonate complexes; Density functional calculations; Zinc

Studies on Pd(1,4-bis(2-hydroxyethyl)piperazine)-dicarboxylic acid complexes as models for carboplatin with structural features enhancing the interaction with DNA - Shehata, Mohamed R.; Shoukry, Mohamed M.; Mabrouk, Mahmoud A.; Kozakiewicz, Anna; van Eldik, Rudi (Journal of Coordination Chemistry, 2019)
[Pd(BHEP)Cl2] and [Pd(BHEP)(CBDA)] complexes, where BHEP = 1,4-bis(2-hydroxyethyl)piperazine and CBDA = cyclobutanedicarboxylate, were synthesized and characterized. [Pd(BHEP) (CBDA)] crystallizes in space group P21, a = 9.5740(8) Å, b = 9.4700(7) Å, c = 9.7890(10) Å, α = 90.00°, β = 113.360(5)°, γ = 90.00°, V = 814.78(13) Å3, Z = 2. The palladium center has a typical square planar geometry with tetrahedral distortion. DFT calculations show good agreement between theoretical and X-ray data. The stability constants and stoichiometry of the complexes formed between various dicarboxylic acids and [Pd(BHEP)(H2O)2]2+ were studied. Dicarboxylic acids form 1:1 and protonated complexes. Inosine forms 1:1, 1:2 and the protonated form of 1:1 complexes. The temperature effect on the formation constant of the cyclobutanedicarboxylate complex was investigated. The hydrolysis of [Pd(BHEP)(H2O)2]2+ and complex formation with cyclobutanedicarboxylic acid are exothermic processes.
CRIS-Team Scopus Importer:2019-07-09
Keywords: 1; 4-Bis(2-hydroxyethyl)piperazine; cylcobutanedicarboxylic acid; DFT calculation; DNA; stability constants; X-ray single crystal

Studies on the Reaction of Iron(II) with NO in a Noncoordinating Ionic Liquid - Begel, Svetlana; Puchta, Ralph; Sutter, Jörg; Heinemann, Frank Wilhelm; Dahlenburg, Lutz; van Eldik, Rudi (Inorganic Chemistry, 2015)
In an earlier study we investigated the reaction of iron(II) chloride with NO in a strongly coordinating ionic liquid 1-ethyl-3-methylimidazolium dicyanamide [emim][dca] and showed that the actual reactive species in solution was [Fe-II(dca)(5)Cl](4-). For the present report we investigated in detail how this reaction could proceed in a noncoordinating ionic liquid 1-ethyl-3-methylimidazolium trifluoromethylsulfonate [emim][OTf]. The donor ability of OTf- is much lower than that of dca(-), such that the solubility of FeCl2 in [emim][OTf] strongly depended on other donors like water or chloride ions present or added to the ionic liquid. On increasing the chloride concentration in [emim] [OTf], the tetrachloridoferrate complex [emim](2)[FeCl4] was formed, as verified by X-ray crystallography. This complex undergoes reversible binding of NO, for which the UV-vis spectral characteristics of the green brown nitrosyl product resembled that found for the corresponding nitrosyl complexes formed in water and [emim][dca] as solvents. A detailed analysis of the spectra revealed that the Fe-NO(7) species has Fe-II-NO center dot character in contrast to Fe-III-NO- as found for the other solvents. The formation constant, however, is much higher than in [emim] [dca], lying closer to the value found for water as solvent. Surprisingly, the Mossbauer spectrum found in [emim][OTf] is very unusual and unsimilar to that found in water and [emim] [dca] as solvents, pointing at a different electron density distribution between Fe and NO in Fe-NO.(7) First, the high isomer shift points to the presence of iron(II) species in solution, thus indicating that upon NO binding no oxidation to iron(III) occurs. Second, the negligible quadrupole splitting suggests a high local symmetry around the iron center. The nitrosyl product is suggested to be [(FeCl3NO)-Cl-II](-), which is supported by electron paramagnetic resonance (EPR) and IR measurements. The nature of the Fe(II) complexes formed in [emim][OTf] depends on the additives required to dissolve FeCl2 in this ionic liquid.

Substitution behaviour of an unusual seven-coordinate iron(III) complex in different solvents - Ivanovic-Burmazovic, Ivana; Hamza, Mohamed; van Eldik, Rudi (Inorganic Chemistry Communications, 2002)
In order to clarify the solution chemistry of 3d metal hepta-coordinate complexes, a detailed mechanistic study of the two-step substitution reaction between the "tweezer-like" iron(III) complex, [Fe(dapsox)(HO)] (Hdapsox=2,6-diacetylpyridine-bis(semioxamazide)), and SCN was performed in water and methanol as solvents. Based on the observed rate law and reported activation parameters (ΔH, ΔS and ΔV) for both reaction steps in aqueous solution, the operation of an I mechanism for the diaqua, an I mechanism for the aquathiocyanato, and an I or D mechanism for the aquahydroxo forms of the Fe(III) complex, is proposed. The operation of a limiting D mechanism is proposed for both reaction steps in methanol as solvent. © 2002 Elsevier Science B.V. All rights reserved.

Substitution versus redox reactions of gold(III) complexes with L-cysteine, L-methionine and glutathione - Durovic, Mirjana D.; Bugarcic, Zivadin D.; Heinemann, Frank Wilhelm; van Eldik, Rudi (Dalton Transactions, 2014)
The influence of tridentate, nitrogen donor ligands, on the stability of gold(III) complexes under physiological conditions was investigated. The interaction of [Au(terpy)Cl](2+) (terpy = 2,2': 6' 2 '' terpyridine), [Au(bpma)Cl](2+) (bpma = bis(pyridyl-methyl) amine), [Au(dien)Cl](2+) (dien = diethylenetriamine) and [AuCl4](-) with the biologically relevant thiols, L-cysteine (L-Cys) and glutathione (GSH), and thioether, L-methionine (L-Met), was studied using UV-Vis spectroscopy, cyclic voltammetry, H-1 NMR spectroscopy and ESI-MS. In this study, the rate constants for substitution reactions between monofunctional gold(III) complexes and sulfur donor ligands in aqueous solution were determined at different initial concentrations of reactants, chloride ions, pH and constant ionic strength. The obtained second-order rate constants for the reaction with L-methionine in the absence of added chloride at pH 2.5 and 25 degrees C follow the sequence (7.5 +/- 0.4) x 10(3) > (4.5 +/- 0.1) x 10(2) > 88.3 +/- 0.8 M-1 s(-1) for the terpy, bpma and dien complexes, respectively, demonstrating that the substitution step could be detected prior to the reduction step. This behavior was expected due to the influence of a decreasing pi-donor ability of the chelate ligands, which slows down the substitution reactions along the series of complexes studied. In order to throw more light on the mechanism of biological activity of gold(III) compounds, such a systematic study was performed for all the mentioned thiols and thioether.

Supramolecular catalysis of sigmatropic rearrangements: Rate acceleration through encapsulation - Fiedler, Dorothea; Zahl, Achim; van Eldik, Rudi; Bergmann, Robert G.; Raymond, Kenneth (ACS National Meeting Book of Abstracts, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.laoc1.supram

Synthesis and characterization of cyanocobalamin conjugates with Pt(II) complexes towards potential therapeutic applications - Porębska, Dominika; Orzeł, Łukasz; Rutkowska-Żbik, Dorota; Stochel, Grażyna; van Eldik, Rudi (Polyhedron, 2023)
The increased affinity of cyanocobalamin (CblCN) for cancer cells provided the basis for its use as a carrier of inorganic cytostatics potentially reducing the side effects of chemotherapy. Our studies were focused on the effect of ligands on the stability of platinum(II) conjugates with CblCN. The synthesis of three selected conjugates containing coordinated chloride ions, water molecules, diethylenetriamine or terpyridine were monitored spectrophotometrically and the formation of desired binuclear complexes were confirmed by MS-ESI, 195Pt NMR and IR spectroscopy. In addition, molecular modelling was applied to determine the geometry and binding energies of the conjugates. According to our results, the expansion of the coordination sphere of the therapeutic metal negatively affects the stability of conjugates with CblCN, which can be considered as expected in the context of their anticipated intercalation ability.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Binuclear complexes; Cyanocobalamin; Drug delivery; Platinum(II) complexes

Synthesis, Biophysical Interaction of DNA/BSA, Equilibrium and Stopped-Flow Kinetic Studies, and Biological Evaluation of bis(2-Picolyl)amine-Based Nickel(II) Complex - Ramzy, Esraa; Ibrahim, Mohamed M.; El-Mehasseb, Ibrahim M.; Ramadan, Abd El-Motaleb M.; Elshami, Fawzia I.; Shaban, Shaban Y.; van Eldik, Rudi (Biomimetics, 2022)
Reaction of bis(2-picolyl)amine (BPA) with Ni(II) salt yielded [(BPA)NiCl2(H2O)] (NiBPA). The Ni(II) in NiBPA bound to a BPA ligand, two chloride, and one aqua ligands. Because most medications inhibit biological processes by binding to a specific protein, the stopped-flow technique was used to investigate DNA/protein binding in-vitro, and a mechanism was proposed. NiBPA binds to DNA/protein more strongly than BPA via a static quenching mechanism. Using the stopped-flow technique, a mechanism was proposed. BSA interacts with BPA via a fast reversible step followed by a slow irreversible step, whereas NiBPA interacts via two reversible steps. DNA, on the other hand, binds to BPA and NiBPA via the same mechanism through two reversible steps. Although BSA interacts with NiBPA much faster, NiBPA has a much higher affinity for DNA (2077 M) than BSA (30.3 M). Compared to NiBPA, BPA was found to form a more stable BSA complex. When BPA and NiBPA bind to DNA, the Ni(II) center was found to influence the rate but not the mechanism, whereas, for BSA, the Ni(II) center was found to change both the mechanism and the rate. Additionally, NiBPA exhibited significant cytotoxicity and antibacterial activity, which is consistent with the binding constants but not the kinetic stability. This shows that in our situation, biological activity is significantly more influenced by binding constants than by kinetic stability. Due to its selectivity and cytotoxic activity, complex NiBPA is anticipated to be used in medicine.
CRIS-Team WoS Importer:2023-01-13

Synthesis, equilibrium, DFT, and docking studies of a homopiperazine complex with dibutyltin(IV) - Khalaf-Alla, Perihan A.; Shoukry, Mohamed M.; Shehata, Mohamed R.; Abdel Wahab, Amira M.; van Eldik, Rudi (Journal of Coordination Chemistry, 2023)
The interaction of dibutyltin(IV) dichloride (DBT) with 1,4-diazacycloheptane (homopiperazine, HP) was investigated. In solutions, the complexes formed a 1:1 complex, its protonated and hydrolyzed forms. The formation constants of the complexes and thermodynamic parameters as ΔH° and ΔS° were estimated. The optimization of the structure of the (Bu)2Sn(HP)Cl2 complex reveals that the tin is six-coordinate in a distorted octahedral geometry, where the two nitrogen atoms of homopiperazine and the two chloride ions are in one plane. The solid (Bu)2Sn(HP)Cl2 complex with homopiperazine was synthesized, and the composition was assigned by elemental micro-analysis and mass spectrum. The complex was investigated by infrared, mass spectra, and thermal measurements. The ligand and its complex were tested against antimicrobial Staphylococcus aureus (+ve), Escherichia coli (−ve), and antifungal Candida albicans and Aspergillus flavus. Anticancer activities of homopiperazine and its dibutyltin(IV) complex were tested against breast cancer cell lines. The molecular docking investigations were performed to know the possible modes of binding to the most active sites of the breast cancer oxidoreductase receptor and those of Escherichia coli.
CRIS-Team Scopus Importer:2023-12-22
Keywords: biological activity; DFT calculation; dibutyltin(IV) complexes; docking studies; equilibrium constants; homopiperazine

Synthesis, structural, equilibrium, anticancer, DNA binding, and computational investigation of binary and ternary palladium(II) complexes based on N-(2-hydroxyethyl)ethylenediamine - Ragab, Mona S.; Shoukry, Mohamed M.; El-Madany, Hanaa M.; Haukka, Matti; van Eldik, Rudi; Khalf-Alla, Perihan A. (Journal of Coordination Chemistry, 2025)
Novel palladium complexes, [Pd(hydten)Cl2] (1) and [Pd(hydten)ox] (2), where hydten = N-(2-hydroxyethyl)ethylenediamine and ox = oxalate, were synthesized. The structure is confirmed using X-ray crystallography for (1) and different physicochemical techniques. A comprehensive analysis was conducted to investigate the composition, stability constants, and speciation curves of [Pd(hydten)(H2O)2]2+ complexes with some bio-ligands such as amino acids, peptides, and DNA constituents. This analysis aims to gain a deeper understanding of the distribution of different species in physiological environments. The interaction with DNA, one of the primary targets for chemotherapeutic drugs, was validated using the UV-Vis spectroscopic technique combined with molecular docking analysis. The geometrical optimization of each compound was performed by density functional theory (DFT), with the complete allocation of HOMO/LUMO electron clouds. In vitro, bio-evaluating the anticancer potency of each compound was accomplished on colon cancer (HCT116), bladder cancer (T24), liver cancer (HepG2), lung cancer (A549) cancer cell lines as well as non-malignant lung cell (WI-38). The [Pd(hydten)Cl2] exhibits enhanced selective cytotoxicity contra the HCT116 malignant cell line (IC50 = 13.87 ± 3.72 μM), lower than that of 5-fluorouracil (5-FU, IC50=23.4 ± 2.4 μM), with minimal effects on healthy WI-38 cells.
CRIS-Team Scopus Importer:2025-02-14
Keywords: anticancer potency; binary and ternary complexes; HCT116 cell line; Pd-N-(2-hydroxyethyl)ethylenediamine complex; WI-38 cell line

The classic "brown-ring" reaction in a new medium: kinetics, mechanism, and spectroscopy of the reversible binding of nitric oxide to iron(II) in an ionic liquid. - Begel, Svetlana; Heinemann, Frank Wilhelm; Stopa, Grzegorz; Stochel, Grazyna; van Eldik, Rudi (Inorganic Chemistry, 2011)
To elucidate the applicability and properties of ionic liquids (ILs) to serve as chemical reaction media for the activation of small molecules by transition-metal complexes, detailed kinetic and mechanistic studies were performed on the reversible binding of NO to FeCl(2) dissolved in the IL 1-ethyl-3-methylimidazolium dicyanamide ([emim][dca]) as a solvent. We report, for the first time, the application of laser flash photolysis at ambient and high pressure to study the kinetics of this reaction in an IL. The kinetic data and activation parameters for the "on" and "off" reactions suggest that both processes follow a limiting dissociative (D) ligand substitution mechanism, in contrast to that reported for the same reaction in aqueous solution, where this well-known "brown-ring" reaction follows an interchange dissociative (I(d)) ligand substitution mechanism. The observed difference apparently arises from the participation of the IL anion as a N-donor ligand, as evidenced by the formation of polymeric [Fe(dca)(3)Cl](x)[emim](2x) chains in the solid state and verified by X-ray crystallography. In addition, infrared (IR), Mössbauer, and EPR spectra were recorded for the monomeric reaction product [Fe(dca)(5)NO](3-) formed in the IL, and the parameters closely resemble those of the FeNO(7) unit in other well-characterized nitrosyl complexes. It is concluded that its electronic structure is best described by the presence of a high-spin Fe(III) (S = 5/2) center antiferromagnetically coupled to NO(-) (S = 1), yielding the observed spin quartet ground state (S(t) = 3/2).

The impact of tripodal chelates on water exchange kinetics and mechanisms: a variable temperature and pressure 17O NMR study to clarify the structure-reactivity relationship in [Fe(II)(L)(H2O2](-) complexes - Maigut, Joachim; Meier, Roland; Zahl, Achim; van Eldik, Rudi (Magnetic Resonance in Chemistry, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dchph.laoc1.theimp

The important role of active site water in the catalytic mechanism of human carbonic anhydrase II - A semiempirical MO approach to the hydration of CO2 - Hartmann, Michael; Merz, Kenneth M.; van Eldik, Rudi; Clark, Timothy (Journal of Molecular Modeling, 1998)
The approach of CO2 to a series of active site model complexes of human carbonic anhydrase II (HCAII) and its catalytic hydration to bicarbonate anion have been investigated using semiempirical MO theory (AM1). The results show that direct nucleophilic attack of zinc-bound hydroxide to the substrate carbon occurs in each model system. Further rearrangement of the bicarbonate complex thus formed via a rotation-like movement of the bicarbonate ligand can only be found in active site model systems that include at least one additional water molecule. Further refinement of the model complex by adding a methanol molecule to mimic Thr-199 makes this process almost activationless. The formation of the final bicarbonate complex by an internal (intramolecular) proton transfer is only possible in the simplest of all model systems, namely [Im(3)Zn(OH)](+). CO2. The energy of activation for this process, however, is 36.8 kcal.mol(-1) and thus too high for enzymatic catalysis. Therefore, we conclude that within the limitations of the model systems presented and the level of theory employed, the overall mechanism for the formation of the bicarbonate complex comprises an initial direct nucleophilic attack of zinc-bound hydroxide to carbon dioxide followed by a rotation-like rearrangement of the bicarbonate ligand via a penta-coordinate Zn2+ transition state structure, including the participation of an extra active site water molecule.
Keywords: human carbonic anhydrase II; semiempirical MO theory; AMl; enzyme catalysis

The influence of terpyridine as ð-acceptor ligand on the kinetics and mechanism of the reaction of NO with ruthenium(III) complexes - van Eldik, Rudi; Heinemann, Frank Wilhelm; et al. (Inorganic Chemistry, 2004)
The kinetics of the unusually fast reaction of cis- and trans-[Ru(terpy)(NH3)2Cl]2+ (with respect to NH3; terpy=2,2':6',2"-terpyridine) with NO was studied in acidic aqueous solution. The multistep reaction pathway observed for both isomers includes a rapid and reversible formation of an intermediate Ru(III)-NO complex in the first reaction step, for which the rate and activation parameters are in good agreement with an associative substitution behavior of the Ru(III) center (cis isomer, k1=618 +/- 2 M(-1) s(-1), DeltaH(++) = 38 +/- 3 kJ mol(-1), DeltaS(++) = -63 +/- 8 J K(-1) mol(-1), DeltaV(++) = -17.5 +/- 0.8 cm3 mol(-1); k -1 = 0.097 +/- 0.001 s(-1), DeltaH(++) = 27 +/- 8 kJ mol(-1), DeltaS(++) = -173 +/- 28 J K(-1) mol(-1), DeltaV(++) = -17.6 +/- 0.5 cm3 mol(-1); trans isomer, k1 = 1637 +/- 11 M(-1) s(-1), DeltaH(++) = 34 +/- 3 kJ mol(-1), DeltaS(++) = -69 +/-11 J K(-1) mol(-1), DeltaV(++) = -20 +/- 2 cm3 mol(-1); k(-1)=0.47 +/- 0.08 s(-1), DeltaH(++)=39 +/- 5 kJ mol(-1), DeltaS(++) = -121 +/-18 J K(-1) mol(-1), DeltaV(++) = -18.5 +/- 0.4 cm3 mol(-1) at 25 degrees C). The subsequent electron transfer step to form Ru(II)-NO+ occurs spontaneously for the trans isomer, followed by a slow nitrosyl to nitrite conversion, whereas for the cis isomer the reduction of the Ru(III) center is induced by the coordination of an additional NO molecule (cis isomer, k2=51.3 +/- 0.3 M(-1) s(-1), DeltaH(++) = 46 +/- 2 kJ mol(-1), DeltaS(++) = -69 +/- 5 J K(-1) mol(-1), DeltaV(++) = -22.6 +/- 0.2 cm3 mol(-1) at 45 degrees C). The final reaction step involves a slow aquation process for both isomers, which is interpreted in terms of a dissociative substitution mechanism (cis isomer, DeltaV(++) = +23.5 +/- 1.2 cm3 mol(-1); trans isomer, DeltaV(++) = +20.9 +/- 0.4 cm3 mol(-1) at 55 degrees C) that produces two different reaction products, viz. [Ru(terpy)(NH3)(H2O)NO]3+ (product of the cis isomer) and trans-[Ru(terpy)(NH3)2(H2O)]2+. The pi-acceptor properties of the tridentate N-donor chelate (terpy) predominantly control the overall reaction pattern.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.laoc1.theinf

The influence of the bridgehead in Saalfrank-type cryptands: prediction of ion selectivity by quantum chemical calculations XII - Balović, Jelena; Ćoćić, Dušan; Puchta, Ralph; Scheurer, Andreas; van Eldik, Rudi (Journal of Coordination Chemistry, 2020)
We examined the cation selectivity of the Saalfrank-type 2-metallocryptands [Ga2R3] and [Fe2R3] (R: 1,1'-(pyridine-2,6-diyl)bis(2-(1H-tetrazol-5-yl)ethan-1-one)) with alkaline and earth alkaline metal ions by means of DFT calculations (B3LYP/LANL2DZp) to obtain a better insight into the influence of the bridge head metal ions responsible for the cryptands ion selectivity. Based on our DFT calculations, notably the application of model equations and geometric features regarding the flexibility of the 2-metallocryptands, we identified K+, Sr2+ and Ba2+ as the best fitting ions. While [Fe2R3] has a cavity a bit larger than [Ga2R3], it prefers the Ba2+ cation, whereas [Ga2R3] selects the smaller Sr2+ cation. The good flexibility of the investigated hosts is provided by the oxygen-donor moieties of the 2-metallocryptands.
CRIS-Team Scopus Importer:2020-07-24
Keywords: cryptand; DFT-study; Selective ion complexation

The ion selectivity of the Goedken-Peng cryptand: prediction of ion selectivity by quantum chemical calculations XVII - Jörg, Julius; Puchta, Ralph; Soldatović, Tanja; Kolenović Serezlić, Majda; van Eldik, Rudi (Journal of Coordination Chemistry, 2024)
The cryptand developed by Virgil L. Goedken and Shie-Ming Peng, along with its interactions with alkaline and alkaline earth metal ions, was investigated using computational chemistry (B3LYP/LANL2DZp) to gain insight into the influence of the flexibility of the chelating N-C-C-N group on overall selectivity towards metal ions. According to DFT calculations, the most suitable cation for the cryptand is Li+, as Na+ is too large and would prefer a longer bond between Na+ and the N-donor. Additionally, the Be2+-N bond in the Goedken-Peng cryptand is excessively long compared to the Mg2+-N-cryptate bond, which is too short. The most effective method for hosting the guest cations is for the cryptand to twist itself, and the flexibility of the chelating N-C-C-N group serves as the most effective structural motive for the Goedken-Peng cryptand to interact with the guest cation.
CRIS-Team Scopus Importer:2024-07-26
Keywords: DFT-study; Goedken-Peng cryptand; selective ion complexation

Theoretical study of the water exchange reaction on divalent zinc ion using density functional theory - Hartmann, Michael; Clark, Timothy; van Eldik, Rudi (Journal of Molecular Modeling, 1996)
The complexes [Zn(H2O)(5)](2+). 2H(2)O and [Zn(H2O)(4)](2+). 2H(2)O turnend out to be the most stable zinc complexes with seven and six water molecules, respectively. This implies that a heptacoordinated zinc(II) complex, where all water molecules are located in the co-ordination sphere, should be energetically highly unfavorable and that [Zn(H2O)(6)](2+) can quite readily push two coordinated water molecules into the solvation sphere. For the pentaqua complex [Zn(H2O)(5)](2+) only one water molecule is easily lost to the solvation sphere, which makes the [Zn(H2O)(4)](2+). H2O complex the most favorable in order to consider the limiting dissociative and associative water exchange process of hexacoordinated zinc(II). The dehydration and hydration energies using the most stable zinc(II) complexes [Zn(H2O)(4)](2+). 2H(2)O, [Zn(H2O)(5)](2+). 2H(2)O and [Zn(H2O)(4)](2+). H2O were calculated to be 24.1 and -21.0 kcal/mol, respectively.
Keywords: ab initio; DFT; zinc complexes; hydration energies

Thermodynamic and kinetic studies on reactions of Pt(II) complexes with biologically relevant nucleophiles - Schiessl, Wolfgang; Summa, Nadine; Puchta, Ralph; van Eikema Hommes, Nico; van Eldik, Rudi (Inorganic Chemistry, 2006)
The effect of different N-N spectator ligands on the reactivity of platinum(11) complexes was investigated by studying the water lability of [Pt(diaminocyclohexane)(H2O)(2)](2+) (Pt(dach)), [Pt(ethylenediamine)(H2O)(2)](2+) (Pt(en)), [Pt-(aminomethylpyridine)(H2O)(2)](2+)( Pt(amp)), and [Pt(N,N'-bipyridine)(H2O)(2)](2+)(Pt(bpy)). Some of the selected N-N chelates form part of the coordination sphere of Pt(II) drugs in clinical use, as in Pt(dach) (oxaliplatin), or are models, regarding the nature of the amines, with higher stability in terms of substitution and hydrolysis of the diamine moiety, as in Pt(en) (cisplatin) and Pt(amp) (AMD473). The effect of pi-acceptors on the reactivity was investigated by introducing one (Pt(amp)) or two pyridine rings (Pt(bpy)) in the system. The pK(a) values for the two water molecules (viz., Pt(dach) (pK(a1) = 6.01, pK(a2) 7.69), Pt(en) (pK(a1) = 5.97, pK(a2) = 7.47), Pt(amp) (pK(a1) = 5.82, PKa2 = 6.83), Pt(bpy) (pK(a1) = 4.80, pK(a2) = 6.32) show a decrease in the order Pt(dach) > Pt(en) > Pt(amp) > Pt(bpy). The substitution of both coordinated water molecules by a series of nucleophiles (viz., thiourea (W), L-methionine (L-Met), and guanosine-5'-monophosphate (5'GMP(-))) was investigated under pseudo-first-order conditions as a function of concentration, temperature, and pressure using UV-vis spectrophotometric and stopped-flow techniques and was found to occur in two subsequent reaction steps. The following k(1) values for Pt(dach), Pt(en), Pt(amp), and Pt(bpy) were found: tu (25 degrees C, M-1 s(-1)) 21 +/- 1, 34.0 +/- 0.4, 233 +/- 5, 5081 +/- 275; L-Met (25 degrees C) 0.85 +/- 0.01, 0.70 +/- 0.03, 2.15 +/- 0.05, 21.8 +/- 0.6; 5'GMP(-) (40 degrees C) 5.8 +/- 0.2, 3.9 +/- 0.1, 12.5 +/- 0.5, 24.4 +/- 0.3. The results for k(2) for Pt(dach), Pt(en), Pt(amp), and Pt(bpy) are as follows: tu (25 degrees C, M-1 s-1) 11.5 +/- 0.5, 10.2 +/- 0.2, 38 +/- 1, 1119 +/- 22; L-Met (25 degrees C, s-1) 2.5 +/- 0.1, 2.0 +/- 0.2, 1.2 +/- 0.3, 290 +/- 4; 5'GMP(-) (40 degrees C, M-1 s(-1)) 0.21 +/- 0.02, 0.38 +/- 0.02, 0.97 +/- 0.02, 24 +/- 1. The activation parameters for all reactions suggest an associative substitution mechanism. The pK(a) values and substitution rates of the complexes studied can be tuned through the nature of the N-N chelate, which is important in the development of new active compounds for cancer therapy.

The self-assembled, atomically defined, flexible and highly tunable bilayered Au/L-cysteine/Cu(II/I) junctions capable of voltage-gated coherent multiple electron/hole exchange - Khoshtariya, Dimitri E.; Dolidze, Tinatin D.; Nioradze, Nikoloz; Laliashvili, Lasha; Shushanyan, Michael; van Eldik, Rudi (Nano Futures, 2021)
Contemporary 2D spintronics (spin-based electronics) is a highly interdisciplinary field with numerous elaborated branches, mostly focusing on atomically thin, layered nano-junctions functionalized within 'dry' or 'wet' cells/cubicles/circuits. The charge carriers' spin-implicated aspects emerge throughout, albeit the most nanotechnologically promising issue (implying the information and energy transfer/storage aspects) among them, is perhaps the uniquely complex yet robust and rather universal phenomenon of a hybrid inter- and intra-layer Bose-Einstein-like (BE) condensation. However, this issue is still not sufficiently explored, especially, in the framework of the 'wet' spintronic domain. Thus, searching for new types of bilayer junctions, and testing of charge/spin allocation and flow within respective nano-devices, is a primary task of current 2D spintronics. In this paper we report on the novel effort towards an extension of the voltage-gated 'wet' 2D spintronics enabled through the self-assembling of bilayered Au/L-cysteine/Cu(II/I) junctions, and their rigorous, yet preliminary current-voltage testing towards the hidden collective spin-related manifestations. Our experimental efforts led to a cascade of rare, uniquely combined observations encompassing the temperature induced, directly visible (irreversibly shape-shifting) single-stage transformation of a CV signal (the natural signature of a voltage-gated interlayer Faradaic process). The ultra-thin shape of the resulting CV signal (unavoidably emerging under certain 'standard' conditions), turned to be readily explainable by the Laviron's general statistical formalism, as due to a multi-charge exchange process with the number of transferred electrons/holes ranging within 4 to 16 (per single elementary act) or even out of this range, being extra tunable via the experimental variables. Furthermore, cathodic and anodic peaks of the 'new' signal are moderately separated from each other and have nearly similar shapes. Additional experiments with a variation of the voltage scan rate, demonstrated the exceptional, very regular decaying of a number of simultaneously transferred electrons/holes (extracted from the peak-shape analysis) on the voltage scan rate; although the former parameters shows some fluctuational scatter in time, and/or from sample to sample. The subsequent multi-theory-based analysis of a whole scope of obtained voltammetric data, allowed for a preliminary conjecturing of the formation of a hybrid BE-like dipolar superfluid encompassing electron/hole-hosting clusters emerging within the bilayer junction. The specific electron/hole ratio within the layers is switchable (gated) by the interlayer potential (voltage) bias. The clusters' dimensions, charge distribution and dynamic exchange are reasonably fluctuative and essentially tunable through the applied potential (i.e. the voltage-gating). New experiments are on their way, revealing unlimited future promises of our current endeavor.
CRIS-Team WoS Importer:2021-01-22

Transition-state effects of ionic liquids in substitution reactions of Pt-II complexes - Weber, Christian; Puchta, Ralph; van Eikema Hommes, Nico; Wasserscheid, Peter; van Eldik, Rudi (Angewandte Chemie International Edition, 2005)
Keywords: density functional calculations; ionic liquids; kinetics; platinum; reaction mechanisms

Triggering water exchange mechanisms via chelate architecture. Shielding of transition metal centers by aminopolycarboxylate spectator ligands - Maigut, Joachim; Meier, Roland; Zahl, Achim; van Eldik, Rudi (Journal of the American Chemical Society, 2008)
Paramagnetic effects on the relaxation rate and shift difference of the O nucleus of bulk water enable the study of water exchange mechanisms on transition metal complexes by variable temperature and variable pressure NMR. The water exchange kinetics of [Mn(edta)(H O)] (CN 7, hexacoordinated edta) was reinvestigated and complemented by variable pressure NMR data. The results revealed a rapid water exchange reaction for the [Mn(edta)(HO)] complex with a rate constant of k = (4.1 ± 0.4) × 10 s at 298.2 K and ambient pressure. The activation parameters ΔH, ΔS, and ΔV‡ are 36.6 ± 0.8 kJ mol, +43 ± 3 J K mol, and +3.4 ± 0.2 cm mol , which are in line with a dissociatively activated interchange (I) mechanism. To analyze the structural influence of the chelate, the investigation was complemented by studies on complexes of the edta-related tmdta (trimethylenediaminetetraacetate) chelate. The kinetic parameters for [Fe(tmdta)(HO)] are k = (5.5 ± 0.5) × 10 s at 298.2 K, ΔH = 43 ± 3 kJ mol, ΔS = ± 30 ± 13 J K mol, and ΔV = +15.7 ± 1.5 cm mol , and those for [Mn(tmdta)(HO)] are k = (1.3 ± 0.1) × 10 s at 298.2 K, ΔH = 37.2 ± 0.8 kJ mol, ΔS = +35 ± 3 J K mol, and ΔV = +8.7 ± 0.6 cm mol. The water containing species, [Fe (tmdta)(HO)] with a fraction of 0.2, is in equilibrium with the water-free hexa-coordinate form, [Fe(tmdta)] . The kinetic parameters for [Fe(tmdta)(H O)] are k = (1.9 ± 0.8) × 10 s at 298.2 K, ΔH = 42 ± 3 kJ mol, ΔS = +36 ± 10 J K mol, and ΔV = +7.2 ± 2.7 cm mol. The data for the mentioned tmdta complexes indicate a dissociatively activated exchange mechanism in all cases with a clear relationship between the sterical hindrance that arises from the ligand architecture and mechanistic details of the exchange process for seven-coordinate complexes. The unexpected kinetic and mechanistic behavior of [Ni(edta′)(HO)] and [Ni (tmdta′)(HO)] is accounted for in terms of the different coordination number due to the strong preference for an octahedral coordination environment and thus a coordination equilibrium between the water-free, hexadentate [M(L)] and the aqua-pentadentate forms [M(L′)(HO)] of the Ni-edta complex, which was studied in detail by variable temperature and pressure UV-vis experiments. For [Ni(edta′)(HO)] (CN 6, pentacoordinated edta) a water substitution rate constant of (2.6 ± 0.2) × 10 s at 298.2 K and ambient pressure was measured, and the activation parameters ΔH, ‡S‡, and ΔV were found to be 34 ± 1 kJ mol, -27 ± 2 J K mol, and +1.8 ± 0.1 cm mol, respectively. For [Ni (tmdta′)(HO)], we found k = (6.4 ± 1.4) × 10 s at 298.2 K, ΔH = 22 ± 4 kJ mol, and ΔS = -59 ± 5 J K mol. The process is referred to as a water substitution instead of a water exchange reaction, since these observations refer to the intramolecular displacement of coordinated water by the carboxylate moiety in a ring-closure reaction. © 2008 American Chemical Society.

Urban Particulate Matter-Induced Decomposition of S-Nitrosoglutathione Relevant to Aberrant Nitric Oxide Biological Signaling - Oszajca, Maria; Wadolek, Anna; Hooper, James; Brindell, Malgorzata; van Eldik, Rudi; Stochel, Grazyna (Chemsuschem, 2019)
Exposure to airborne particulate matter (PM) is associated with hazardous effects on human health. Soluble constituents of PM may be released in biological fluids and disturb the precisely tuned nitric oxide signaling processes. The influence of aqueous extracts from two types of airborne urban PM (SRM 1648a, a commercially available sample, and KR PM2.5, a sample collected " in-house" in Krakow, Poland) on the stability of S-nitrosoglutathione (GSNO)was investigated. The particle interfaces had no direct effect on the studied reaction, but extracts obtained from both samples facilitated NO release from GSNO. The effectiveness of NO release was significantly affected by glutathione (GSH) and ascorbic acid (AscA). Examination of the combined influence of Cu2+, Fe3+, and reductants on GSNO stability revealed copper to be the main GSNO decomposing species. Computational models of nitrosothiols interacting with metal oxide substrates and solvated metal ions support these claims. The study stresses the importance of the interplay between metal ions and biological reductants in S-nitrosothiols decomposition.
CRIS-Team WoS Importer:2019-03-12

Volume profile analysis for the reversible binding of superoxide to form iron(II)-superoxo/iron(III)-Peroxo porphyrin complexes - Dürr, Katharina L.; Jux, Norbert; Zahl, Achim; van Eldik, Rudi; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2010)
The one-electron reduced iron(II)-dioxygen adduct, Fe-O , is known to be an important intermediate in the catalytic cycle of heme (mono)oxygenases. The same type of species, considered as Fe-peroxo, can be formed in a direct reaction between a Fe center and superoxide. In a unique high-pressure study of the reaction between superoxide and the Fe complex of a crown ether porphyrin conjugate in dimethylsulfoxide (DMSO), the overall Fe -superoxide interaction mechanism could be visualized and the nature of all species that occur along the reaction coordinate could be clarified. The equilibrium between the low-spin and high-spin forms of the starting Fe complex was quantified, which turns out to be the actual activation step toward substitution and subsequent inner-sphere electron transfer reactions. The constructed reaction volume profile demonstrates that the reaction product consists of Fe-peroxo and Fe -superoxo species that exist in equilibrium, which can better account for the versatile reactivity of Fe-O adducts toward different substrates. © 2010 American Chemical Society.

Water exchange controls the complex-formation mechanism of water-soluble iron(III) porphyrins: Conclusive evidence for dissociative water exchange from a high-pressure 17O NMR study - Schneppensieper, Thorsten; Zahl, Achim; van Eldik, Rudi (Angewandte Chemie International Edition, 2001)

Water exchange reactions and hydrolysis of hydrated titanium(III) ions. A density functional theory study - Hartmann, Michael; Clark, Timothy; van Eldik, Rudi (Journal of Physical Chemistry A, 1999)
The structure and water exchange mechanism of hexahydrated Ti(III), its hydrolysis, and the water exchange mechanism of analogous hydroxo-aqua complexes have been studied using density functional theory (DFT) calculations. Isolated metal-aqua and metal-hydroxo clusters corresponding to the gas-phase (T = 0 K) were used to approximate the model reactions. The structure of [Ti(H2O)(6)](3+) was found to have C-i symmetry and Ti-O bond lengths of 2.094 Angstrom. The water exchange reaction of this complex follows an (almost) limiting A mechanism with an energy of activation of 15.8 kcal mol(-1). The hydrolysis of hexahydrated Ti(III) was modeled by an in vacuo proton-transfer process between water molecules of the first and second coordination spheres of [Ti(H2O)(6)](3+).H2O. This process was found to be activationless and leads to the unusually stable dication:cation pair [Ti(H2O)(5)(OH)](2+).H3O+, which is lower in energy than the reactant by 4.5 kcal mol(-1). Only a weak structural influence, indicated by a slight increase in the mean value of the Ti-O bond lengths of water molecules in the first coordination sphere, is observed when the hydroxo ligand is formed. The water exchange reactions of the corresponding hydroxo-aqua complexes [Ti(H2O)(5)(OH)](2+) and [Ti(H2O)(5)(OH)](2+).H2O, respectively, were found to proceed via limiting D mechanisms. The energies of activation for the exchange of the water molecule in the trans-position to the hydroxo ligand were calculated to be only 9.8 and 7.2 kcal mol(-1), respectively. This, however, implies that the apparently weak influence of coordinated hydroxide still results in a significant reduction in the energy barrier for the water exchange reaction and also leads to a complete changeover in the preferred exchange pathway from A to D.